Crack-induced response of steel liners in lined rock caverns for underground energy storage - Xinyu Liu; Jianping Yang; Zi-ang Xia; Xiang Ci; Peng Li; Weizhong Chen (Tunnelling and Underground Space Technology, 2027)

Closure of the Eastern Paleo-Asian Ocean: Deformation and geodynamics - Qi’ang Fang; Yongjiang Liu; Qingbin Guan; Zhaoxu Chen; Boran Liu; Sanzhong Li (Gondwana Research, 2026)

Integrating grazing intensity regulation and livestock mobility restoration: A practical test for China’s next-generation rangeland policies - Jianguo Xue; Zunlan Luo; Zhang Chen; Ping Ge; Junchen Lv; Jianhui Huang; Ang Li (Agriculture, Ecosystems & Environment, 2026)

Three-dimensional settling map for intelligent detection of activated sludge (AS) properties and health evaluation of AS based wastewater treatment - Jie Lei; Zhe Liu; Guoning Huang; Jiaxuan Wang; Rushuo Yang; Ying Du; Tianyu Han; Zhuangzhuang Yang; Ang Li; Yongjun Liu; Zhenmin Luo; Rong Chen (Water Research, 2026)

Improving freshwater ecosystem assessment via the integration of eDNA-based multitrophic biotic groups - Minglei Ren; Xue Gong; Mengdie Geng; Ting Hu; Ang Hu; Li Chen; Guangjie Chen; Jianjun Wang (Water Research, 2026)

Synergistic surface engineering enables high-efficiency and stable operation of low-bromine wide-bandgap perovskite solar cells - Zhenzhen Peng; Zhimin Fang; Yi Zhang; Rongyao Lv; Yu-Ang Liu; Dehan Li; Bairu Li; Luozheng Zhang; Shuang Chen; Shangfeng Yang; Jianning Ding (Chemical Engineering Journal, 2026)

Glucose mitigates propionate toxicity and enhances odd-chain fatty acid production in Schizochytrium sp.: mechanistic insights and rational fermentation design - Ziliang Deng; Zhao Zhang; Shuang Sun; Zihan Meng; Yaqi Xu; Min Gao; Jiayi Li; Ang Li; Weijia Li; Dongzhe Sun (Bioresource Technology, 2026)

Overcoming thermodynamic limitations on anaerobic methanogenesis via DSF/c-di-GMP enhanced indirect interspecies electron transfer - Chunyan Li; Jia Meng; He-Ping Zhao; Ang Li (Water Research, 2026)

Unlocking the potential in municipal reclaimed water electrolysis for hydrogen production: Identification of the primary water matrix - Zongping Wang; Haoran Chen; Zhenbin Chen; Yunfei Li; Ang Lu; Yujie Cheng; Guosen Zhang; Ge Li; Shunjie Zhu; Lin Li; Lizhi Huang; Jiakun Fang; et al. (Water Research, 2026)

Dimensional reduction of hydrogen-bonding networks induced by hierarchical confinement to promote ultra-fast adsorption of hydrated ions to targeted sites - Meng Du; Zhiqiang Sun; Aiwen Wang; Ang Li; Jun Ma (Water Research, 2026)

MAAI -YOLOv11s: A novel microplastic and nanoplastic particle classification and detection method in microfluidic chip with an improved YOLOv11s model - Kai Zhao; Junzhu Yao; Ang Li; Xuyang Wang; Jingbo Li; Yiyang Huo; Jie Chen; Junsheng Wang (Journal of Water Process Engineering, 2026)

Mussel-inspired construction of superhydrophilic/underwater superoleophobic PTFE membranes using a novel ε-polylysine-based modification for efficient oil-water separation - Xin Wu; Chenyang Li; Shuiling Hong; Ang Gao; Haoming Duan; Wei Li; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

Heat transfer through loess cover layers above thermally active coal gangue zones for vegetation root-zone protection: Large-scale experiments and numerical simulation - Ang Li; Chengkun Song; Wenzhuo Qiu; Jing Fang; Min Li; Bole Yi (Journal of Environmental Chemical Engineering, 2026)

Synergistic TP/APTES coating on PBT membrane enables superhydrophilicity and efficient oil-water separation - Shuiling Hong; Chenyang Li; Xin Wu; Ang Gao; Haoming Duan; Man Liu; Sijia Zhang; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

Canned seafood as a potential source of microplastics exposure with taxon-specific partitioning and packaging-derived contamination - Xinyi Li; Shihan Xu; Jin Qian; Binhan Li; Li'ang Li; Chengming Zhang; Fangzheng Zhang; Menghong Hu; Moslem Sharifinia; Nisha Singh; Jae-Seong Lee; James Kar-Hei Fang; et al. (Environmental Pollution, 2026)

Biomimetic multistage drug delivery system for reversing chemoresistance in osteosarcoma - Xingyin Li; Shaojie Xu; Youyun Peng; Ziliang Su; Sining Wang; Ang Li; Yaying Du; Zengwu Shao; Xin Huang (Chemical Engineering Journal, 2026)

A source-reduction process via mechanical activation assisted K2SO4 roasting and closed-loop recycling of potassium salt for efficient lithium extraction from lepidolite - Dong-qi Song; Shu-hao Dong; Long-long Zhou; Zi-ang Si; Shuai-bo Geng; Huan Li; Hui Guo (Chemical Engineering Journal, 2026)

Enhancing power-to-hydrogen efficiency: A streamline-shaped flow channel design for alkaline water electrolyzers verified using a microfluidic experimental platform - Xiudong Duan; Ziyu Liu; Ang Lu; Jiachang Wan; Fan Chen; Desheng Li; Xiaomeng Ai; Chaolong Song; Jiakun Fang (Chemical Engineering Journal, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

Multi-objective optimization for multi-zone HVAC system via physics-integrated predictive control framework with CFD-assisted visualization - Fangli Hou; Jack C.P. Cheng; Cong Huang; Ang Li; Helen H.L. Kwok; Zhaoji Wu (Building and Environment, 2026)

Identification, characterization and biogenic fungicide screening of Macrophomina phaseolina (Tassi) Goid. causing root rot in Atractylodes lancea (Thunb.) DC. - Haonan Shen; Ruixin Ju; Ang Li; Min Tang; Xiaomeng Fei; Yueyu Ye; Lixia Wang; Fang Tian; Wei Gu (Australasian Plant Pathology, 2026)

Mitigation of biogenic acidification via increased total alkalinity in high stocking density culture waters of Strongylocentrotus intermedius: Effects on growth and metabolism - Jiamin Li; Jiaqi Li; Minghui Jiao; Yadong Wang; Ang Li; Suyan Xue; Lulei Liu; Yuze Mao (Aquaculture, 2026)

Interfacial modulation of oil microdroplets via 1O2 stimulated by exposed Fe clusters catalyzing ozonation of 1-adamantanecaboxylic acid for destabilization - Xuan Qu; Qian Xu; Zhiqiang Chen; Ang Li (Water Research, 2026)

Temperature-sensitive chlorophyll degradation uncouples degreening from other ripening traits and guides postharvest quality improvement in kiwifruit - Ameer Hamza Hafeez; Zheng Zhang; Ang Li; Zhebin Zeng; Yan Chen; Tiantian Li; Xiaomei Ji; Yi Wang; Zhongyan Wang; Yunjiang Cheng; Hamza Sohail; Di Feng; et al. (Postharvest Biology and Technology, 2026)

An integrated optimization framework for voyage and fleet allocation planning in Ro-Ro transport under multiple ship types and contract requirements - Chuanzhong Yin; Xinyi Yao; Luoyi Chen; Lin Li; Zi-Ang Zhang (Ocean Engineering, 2026)

Zinc co-exposure with different antibiotic classes drives distinct microbial community restructuring in activated sludge - Yu Ang Li; Shijie Dong; Yongchao Li; Wei Wen; Mengbo Yuan; Jiangxiao Luo; Bin Shi; Renxin Zhao (Journal of Hazardous Materials, 2026)

Using machine learning models to estimate ecotoxicity effect factors for various nanomaterials in life cycle assessment - Xiao Li; Yuan Yuan; Ang Li; Wei Sun; Weichun Ma (Journal of Hazardous Materials, 2026)

Coupled molybdenum and iron isotopes distinguish seawater and hydrothermal inputs to seep carbonates - Hangyu Nan; Xiaoming Miao; Hongxiang Guan; Ang Li; Zhilei Sun; Thomas J. Algeo; Davide Oppo; Nengyou Wu; Sanzhong Li (Geochimica et Cosmochimica Acta, 2026)

Hypoxia-induced downregulation of cAMP drives Ganoderic acid biosynthesis and restricts biofilm development in Ganoderma lucidum - Siyi Wang; Li Tian; Faqin Li; Qin Wang; Yanan Tan; Yanda Ning; Xuewei Cao; Yueqian Liu; Jiaolei Shangguan; Huihui Li; Ailiang Jiang; Mingwen Zhao; et al. (Food Research International, 2026)

Activating lattice oxygen in Ni-doped SnO2 to break surface confinement for high-performance hydrogen sensing - Meili Wu; Yanbai Shen; Sikai Zhao; Ang Li; Jinzhou Bai; Qiang Zhao; Wenbao Liu; Zhenyu Yuan; Fanli Meng (Chemical Engineering Journal, 2026)

A multifunctional polar additive enables highly reversible zinc anodes via synergistic regulation of water chemistry, deposition behavior, and interphase stability - Yufei Wang; Pengtao Wang; Ang Li; Ce Liang; Kaifeng Yu (Chemical Engineering Journal, 2026)

Tissue-specific energy trade-off strategies in Mytilus coruscus under combined stress of nano-TiO2 and marine heatwaves - Bing Liu; Sijie Fan; Menghong Hu; Li'ang Li; Mojiang Zhang; Xinyue Li; Moslem Sharifinia; Piotr Maszczyk; Nisha Singh; Waiho Khor; Hanafiah Fazhan; Wei Liu; et al. (Aquatic Toxicology, 2026)

Astronomically forced climate change during the Middle Oligocene-Early Miocene in the Pearl River Mouth Basin, Northern South China Sea - Shizhen Jia; Yanzhen Li; Mengqing Shang; Rui Liu; Linzhen Hu; Yongming Zhang; Xiuju Xing; Zi’ang Yang (Marine Geophysical Research, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Plant diversity gradients modulate thermo-physiological and psychological restoration in urban green spaces: A field study in China’s cold region - Chengsheng Wang; Yulan Li; Yuxin Jin; Ang Li; Miaosen Zhang; Wenxia Huang; Bo Hong (Urban Forestry & Urban Greening, 2026)

Climate risk, cross-regional power transmission, and urban energy system resilience: Evidence from the regional level in China - Ang Li; Bin Li (Utilities Policy, 2026)

Effects of age-related gastrointestinal conditions on the digestion of myofibrillar protein-stabilized fish oil oleogel emulsions - Yumin Niu; Li Hu; Zongyuan Han; Hongli Wang; Yu-ang Jiang; Xueyan Cao; Jun-Hua Shao (Food Research International, 2026)

A sensory-calibrated electronic nose method for odor intensity quantification and grade identification in refrigerators - Shiwen Cheng; Li’ang Yin; Xiao Ye; Xiaozheng Liu; Yumei Qin; Yaqing Song; Suyun Zhang; Tengfei Yu; Chonghui Zhang; Shiyi Tian (Food Research International, 2026)

A mimetic drug delivery system using graphene oxide as a component carrier in denitrification: Enhancing long-term stable carbon release and electron transfer capacity of carbon source materials - Ziyi Wang; Yawen Wang; Zhiqiang Chen; Jia Meng; Zhihao Gan; Peng Liu; Ang Li (Chemical Engineering Journal, 2026)

Methane production in the stems of living trees in subtropical forests - Zhi-Ping Wang; Josep Barba; Jian-Guo Xue; Xiang-Cheng Mi; Ang Li; Zhen-Ying Huang; Shi-Jie Han (Planta, 2026)

Research on Shear Creep-Impact Mechanical Model of Anchored Jointed Rock Masses with Combined Macro–Meso Parameters Under Constant Normal Stiffness Boundary Conditions - Jianhua Zhou; Yang Song; Heping Wang; Jingjing Duan; Wan Li; Ang Li (Rock Mechanics and Rock Engineering, 2026)

Cajaninstilbene acid induced apoptosis and cell cycle arrest in glioblastoma multiforme through mitochondrial ROS–mediated MAPK pathways - Yong-Ang Li; Tian-Zeng Bian; Hong Li; Jia-Wen Li; Liu-Tao Ma; Hao-Di Wu; Shuai Chen; Jia-Yi Chen; Hao Zeng; You-Bing Mao; Peng Wang; Qi Qiao (Food and Chemical Toxicology, 2026)

Designing hard-soft carbon composite anodes via a normalized pore volume-mass matching strategy for high-performance sodium storage - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Xiaofeng Zhang; Haiyan Liu; Chengwei Fan; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

A Physics-Data Co-Driven Approach for Blast-Induced Flyrock Control - Ang Li; Ningning Wang; Yaosheng Liu; Danial Jahed Armaghani; Biao He (Natural Resources Research, 2026)

The Effects of Intraoperative Hypotension on Postoperative Acute Kidney Injury and Myocardial Injury: A Systematic Review and modelling study - Jiaxin Zhao; Xuan Li; Yunfei Lv; Rui Zhang; Ang Li; Gang Dong (Phenomics, 2026)

Quantitative analysis of the mechanical behavior of granular sands subjected to particle pre-crushing - Wenli Lin; Guixu Li; Zhening Guo; Ting Yao; Ang Liu; Jiren Xie (Transportation Geotechnics, 2026)

Biofilm-based immobilized fermentation of Bacillus subtilis coupled with Ni2+-NTA in situ adsorption for efficient hydrolysis of silkworm pupa protein - Xin-Chen Li; Zhi-Ang Zhang; Yi-Nan Cao; Chao Deng; Fu-Ling Wang; Hai-Fei Zhang; Richard Ansah Herman; Le-Yun Yang; Jun Wang (Sustainable Chemistry and Pharmacy, 2026)

Optimization design of energy characteristics and broadband noise source mechanisms of annular propellers - Lei Zhang; Wentian Pang; Ang Li; Lucai Wang; Zhenwei Huang (Ocean Engineering, 2026)

Robust gut microbiota as a key protective barrier for Ruditapes philippinarum survival following an extreme-rainfall disturbance - Longzhen Liu; Lulei Liu; Ang Li; Zirong Liu; Suyan Xue; Jiaqi Li; Yuze Mao (Marine Environmental Research, 2026)

Transcriptional and functional dissection of cytochrome P450 and ABC transporters underlying tobacco tolerance in Lasioderma serricorne - Junaid Zafar; Shuhao Zhang; Rana Fartab Shoukat; Ling Huang; Ang Li; Zhanpeng Zhu; Ziling Wan; Yanqing Li; Xuewei Zhang; Chen Peng; Shuai Zhong; Xiaoxia Xu; et al. (Journal of Insect Physiology, 2026)

Enhanced treatment of high-algae water and membrane fouling mitigation by SPDA@MIL-101-modified polyethersulfone ultrafiltration membranes with magnetic field regulation and magnetic flocculant assistance - Meng Yao; Ang Li; Zhilin Ran; Xiaoqing Dong; Ruiyan Xiang; Ting Chen; Gang Liu (Journal of Environmental Chemical Engineering, 2026)

Microbial community shift and functional reorganization from influent to effluent in wastewater treatment plants on the Qinghai–Tibet Plateau - Yongchao Li; Bin Shi; Di Li; Yu-Ang Li; Mengbo Yuan; Jiangxiao Luo; Shijie Dong; Wei Wen; Renxin Zhao (Journal of Environmental Management, 2026)

Characterizing typhoon-disturbed biomass dynamics using multitemporal LiDAR, high-resolution imagery, and deep learning in cool-temperate forest, northern Japan - Ang Li; Tomomichi Kato; Hantao Li; Long Duc Nguyen; Masato Hayashi; Ram Avtar; Tatsuro Nakaji (Forest Ecology and Management, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Molecular bridging-enables fully π-conjugated carbonyl polymers for selective ammonium ion capture in capacitive deionization - Yuxi Huang; Jun Yang; Hao Zhou; Tingliang Yuan; Jinyang Peng; Xinran Zhao; Chunyan Li; Minjie Shi; Edison Huixiang Ang (Chemical Engineering Journal, 2026)

Crafting cellulose hollow microspheres with cellulose nanosheets - Wenxuan Lei; Heng Huang; Ruobing Liang; Guoping Li; Pan Chen; Jiechun Xiang; Ang Lu (Carbohydrate Polymers, 2026)

Interactive effects of noise and odor on construction workers' environmental perception and cognitive performance amid outdoor thermal stress - Zi Li; Xinyue Zhang; Zijing Peng; Ran Xing; Ang Li; Bo Hong (Building and Environment, 2026)

MPFT-UNet: A Boundary-Refined and Multi-Scale Dynamic Fusion Network for UAV-Based Port Ship Segmentation - Mengna Shi; Xiulin Qiu; Ang Li; Yuwang Yang; Yaqi Ke; Yilan Chen (Journal of Marine Science and Engineering, 2026)
Ship semantic segmentation based on unmanned aerial vehicle (UAV) imagery has important application value in maritime scenarios such as marine surveillance, port management, and maritime safety. However, UAV images often contain large scale variations of ships, a high proportion of small targets, and complex background interference, including sea surface reflections, waves, and clouds. These factors make accurate segmentation and boundary localization difficult. To address these issues, this paper proposes a UAV-based ship semantic segmentation network, termed MPFT-UNet. The network introduces a Multi-scale Dynamic Sparse Cross-gating (MDSC) module to improve the representation of small targets. A Boundary Supervision Refinement (BSR) module is used to enhance boundary delineation. In addition, a Transformer-based Feature Fusion (FFT) module is applied at the bottleneck layer to strengthen global semantic representation. Experimental results show that MPFT-UNet achieves better performance than existing methods across multiple evaluation metrics. The model obtains an IoU of 0.8365, Dice coefficient of 0.9028, Recall of 0.8881, and AP of 0.95731. These results indicate stable segmentation performance under complex maritime conditions. Compared with the baseline U-Net model, the IoU is improved by approximately 5.1%.

Centennial-scale evolution of organic carbon sources and burial in the northern coastal mud area of the Shandong Peninsula and its response to human activities - Qing Xu; Yao Huang; Zhe Xu; Jiawei Ding; Cunwang Lin; Ang Li; Jiandong Qiu (Frontiers in Marine Science, 2026)
The mud area off the northern Shandong Peninsula is a critical region for sediment and organic carbon (OC) burial in the Yellow Sea. Based on a sediment borehole with 210 Pb-derived sedimentation rate of 0.63 cm/a, multiple proxy parameters including grain size, total organic carbon (TOC), total nitrogen (TN), stable carbon isotope (δ 13 C), and nitrogen isotope (δ 15 N) were analyzed to reconstruct centennial-scale OC sources and burial. Results show that the sediments are dominated by clayey silt, with stable grain-size composition over the past century. OC is derived from mixed marine and terrestrial sources, with marine phytoplankton contributing 56.3% on average. TOC content ranges from 0.31% to 0,41%, showing an increasing trend since 1950, with δ¹ 5 N rising from 4.35‰ to 5.41‰, indicating enhanced marine productivity driven by increased nutrient inputs and mariculture. Terrestrial OC contribution decreased from 52.6% to 34.7%, largely due to dam construction on the Yellow River, followed by a slight recovery in recent decades. Compared to the central South Yellow Sea, our study area exhibits lower OC accumulation rates but stronger sensitivity to human activities due to its proximity to the Yellow River source. This study provides scientific evidence for coastal carbon sink assessment under Anthropocene pressures.

Hydrogen sulfide maintains banana postharvest quality by antagonizing ethylene and enhancing antioxidant properties in Musa nana Lour - Xue-Ting Cheng; Yan-Hong Li; Yun Ge; Zhuo Han; Yi-Ang Feng; Ying-Zhi Zhang; Kang-Di Hu; Gai-Fang Yao; Pedro García-Caparros; Hua Zhang (Food Control, 2026)

Surface-engineered Mn–Prussian Blue analogue with dual redox centers for high-performance hybrid capacitive deionization - Jianeng Ji; Jun Yang; Zhiqiang Wu; He Ren; Hao Fu; Chunyan Li; Minjie Shi; Edison Huixiang Ang (Chemical Engineering Journal, 2026)

Carrier-free nanoparticles derived from Huanglian Jiedu decoction target ATP5F1C to eliminate senescent cells and ameliorate pulmonary fibrosis - Ying Zhang; Lirun Zhou; Yajian Li; Weiling Wang; Tong Yang; Qianyu Zhang; Hechen Tang; Jiayun Guo; Ling Huang; Chen Wang; Zheng Chu; Ang Ma; et al. (Chemical Engineering Journal, 2026)

Physical exercise protects cardiovascular fitness in long-term spaceflight: what have we learned? - Zi’ang Zhang; Wenjuan Xing; Guiling Wu; Xing Zhang; Jia Li; Yingxian Li; Feng Gao (Science China Life Sciences, 2026)

Serum Endogenous Opioid Levels are Associated with Self-Injury Severity in Adolescents with Non-Suicidal Self-Injury and Comorbid Depression - Jin-Jun Ding; Xiao-Li Liu; Ang Li; Yi-Yao Liang; Yu-Bo Wang; Xiao-Na Zhu; Jie Li; Jie Weng; Lan Yan; Wen-Wen Duan; Zi-Chen Zhang; Ti-Fei Yuan; et al. (Neuroscience Bulletin, 2026)

Patterns and mechanisms of programmed cell death in bloom-forming Microcystis aeruginosa induced by potent allelochemical juglone - Xu Yang; Jinyuan Chen; Ang Gao; Jinting Li; Yulu Hu; Haiying Wang; Xin Zhang (Journal of Oceanology and Limnology, 2026)

Depth Stratification Shapes Viral Diversity, Interactions, and Metabolic Potential in a Deep Freshwater Lake - Zong Li; Minglei Ren; Ang Hu; Fanfan Meng; Jianjun Wang (Molecular Ecology, 2026)
Deep freshwater lakes exhibit distinct microbial community stratification across depth gradients, which plays important roles in biogeochemical cycling and ecosystem stability. As crucial regulators of microbiome composition and function, viruses may play key ecological roles in these stratified systems, yet their distribution patterns and ecological significance in deep‐lake surface sediments remain poorly understood. Here, we assessed viral community dynamics and functional potential across the entire water depth gradient (0–155 m) of Fuxian Lake using metagenomics from 44 surface sediment samples. A total of 11,523 viral OTUs were recovered, with only 18% annotated to the family level and approximately 93% classified as putatively lytic. Viral communities showed systematic depth‐related shifts across multiple dimensions. Specifically, alpha diversity, community turnover, and stochastic assembly processes increased significantly with water depth, accompanied by enhanced lytic virus dominance and larger genome sizes. Predicted virus‐host association networks transitioned from highly connected and generalized at shallow depths to increasingly sparse and specialized at greater depths. Virus‐encoded auxiliary metabolic genes showed significantly increasing abundance with water depth, along with functional shifts from host defense to enhanced biosynthesis and energy metabolism, especially regarding carbon fixation and organic matter degradation. Collectively, these results highlight the importance of water depth gradients in structuring viral communities within surface sediments and expand our understanding of viral ecological functions in deep lake ecosystems.

Effect of host switching on the parasitic performance of Habrobracon hebetor (Hymenoptera: Braconidae) against Ephestia elutella in stored tobacco - Jingtian Xue; Yao Huang; Houding Ou; Yi Mao; Ang Li; Liang Wang; Maofa Yang (Crop Protection, 2026)

Thiophene-based styrene derivative improves colitis symptoms in DSS-induced BALB/C mice through AhR-mediated gut barrier function and inflammatory responses - Ang-Kun Yang; Yong-Liang Li; Yan-Ying Chen; Yan Liu; Zhi-Yun Du; Chang-Zhi Dong; Bernard Meunier; Hui-Xiong Chen (Toxicology and Applied Pharmacology, 2026)

The dual nature of neuroticism: distinct dimensions impact longevity and well-being - Yini He; Jing Xiao; Ke Hu; Tian Gao; Yan Yan; Yu Yu; Lei Wang; Kaixin Li; Wenkun Lei; Kun Zhao; Changsheng Dong; Xiaohan Tian; et al. (Science Bulletin, 2026)

Chlorine dioxide fumigation induces transcriptomic and metabolomic reprogramming enhancing resistance to soft rot in kiwifruit - Ang Li; Shuang Luo; Di Feng; Xiaoya Chen; Zhidan Zhao; Tiantian Li; Yunhe Meng; Xiaoqin Yang; Yunjiang Cheng; Yunliu Zeng (Postharvest Biology and Technology, 2026)

Sustainability potential of landfill mining and resource recovery: Evidence from plant cases, provincial data, and life cycle assessment in China - Ang Wang; Jing Li; Wenxin Xue; Yin Li; Hanqiao Liu; Jifeng Zhao; Qianlong Han (Journal of Environmental Chemical Engineering, 2026)

Mitigating Dyeing Industry Water Pollution Through Advances in Chitosan-Based Adsorbents - Swee Pin Yeap; Yvonne Ang; Shuen Lam; Swee Sen Teo; Lai Huat Lim; Li Sze Lai; Hui Suan Ng; Zeinab Abbas Jawad; Kah Hon Leong; Zaher Mundher Yaseen (Water Conservation Science and Engineering, 2026)

Coupled SPH-FEM modelling from landslide surges to dynamic response of concrete dams - Hui Jiang; Yao-Yun Yuan; Jin-Ting Wang; Zi-Ang Wang; Xiu-Li Du (Bulletin of Engineering Geology and the Environment, 2026)

HUTG: a next-generation IGS real‑time combined GIM via two‑step global and regional correction with robust weighting from HENU and UPC‑IonSAT - Kualong Xu; Qi Liu; Manuel Hernández-Pajares; Enric Monte-Moreno; Heng Yang; Germán Olivares-Pulido; David Roma-Dollase; Alberto García-Rigo; Ningbo Wang; Zishen Li; Ang Liu; Clément Ubelmann; et al. (GPS Solutions, 2026)

Wollastonite enhances microbial diversity and ecological network stability - Yanzhi Wang; Yongfeng Wang; Ronghua Kang; Chunjie Tian; Guochen Li; Feifei Zhu; Ang Wang; Geshere Abdisa Gurmesa; Chenxia Su; Chang Liu; Dong Liu; Zhi Quan; et al. (Applied Soil Ecology, 2026)

Impact of high-frequency atmospheric noise on ENSO predictability - Guangyu Chi; Ang Li; Yishuai Jin; Xiaopei Lin (Acta Oceanologica Sinica, 2026)

Topography‐Mediated Soil Moisture Controls Forest Hillslope‐Scale NO and N 2 O Emissions - Kai Huang; Dongwei Liu; Yihang Duan; Di Wu; Geshere Abdisa Gurmesa; Ronghua Kang; Jingwen Xu; Xue Li; Yuqi Liu; Erik A. Hobbie; Xiaoming Fang; Chenxia Su; et al. (Global Change Biology, 2026)
Temperate forests are key terrestrial carbon sinks, yet their capacity to sequester carbon is often limited by nitrogen (N), a nutrient whose availability is declining in many ecosystems. Among factors contributing to declining N availability, climate‐driven changes in soil hydrology could force N loss via the emission of both nitric oxide (NO) and nitrous oxide (N 2 O); however, forecasting these losses is challenging because they are regulated by soil moisture, a factor that regulates microbial activity and substrate availability but varies significantly across space and time. Here, we ask: how do topography‐driven soil moisture gradients and changes in seasonality (e.g., spring–thaw cycles) mediate hillslope‐scale N emissions? We measured over 2 years of high‐resolution in situ NO and N 2 O fluxes from 16 automated chambers deployed along a topographic gradient in a temperate forest to show that soil moisture gradients governed spatial and temporal patterns of soil N emissions. These gradients produced tradeoffs in process controls, whereby temperature regulated N emissions in drier upper positions, giving way to soil moisture regulating microbial pathways and emissions in wetter downslope positions. We then used these relationships among soil moisture, temperature, and N availability to develop models for predicting hillslope‐scale NO + N 2 O losses. Annual emissions averaged 0.2 kg NO‐N ha −1 (range: 0.1–0.3) and 1.0 kg N 2 O‐N ha −1 (range: 0.7–4.9), with N 2 O showing a stronger response to moisture‐driven changes than NO. The spring freeze–thaw period accounted for 15%–26% of NO and 24%–58% of N 2 O annual emissions, with the highest emissions measured consistently at lower topographic positions. These findings establish topography‐mediated hydrology as a primary control of forest soil N dynamics and gaseous N emissions, reducing uncertainty in forecasts of hillslope‐scale N losses under a changing climate.

The DNA-binding protein PfAP2-V regulates erythrocyte invasion and pathogenesis of the human malaria parasite Plasmodium falciparum - Yanxin Zhang; Changhong Wang; Qilong Li; Ang Li; Yutao Zhang; Ziwei Su; Liying Yu; Kexin Zheng; Tong Liu; Ning Jiang; Yiwei Zhang; Xiaoyu Sang; et al. (Science China Life Sciences, 2026)

Dynamic Response and Operational Performance of an Integrated Floating Wind Turbine–Net Cage Platform - Xing-Hua Shi; Qiang Ang; Jing Zhang; Honglong Li; Chunhan Wu; Shan Wang (Journal of Marine Science and Engineering, 2026)
This study investigates the floating wind turbine (FWT)–Net cage integrated platform, where the net cage is rigidly connected to the FWT foundation. The platform is numerically modeled using time-domain simulations in OrcaFlex V11.1, based on representative environmental conditions of the South China Sea. The operational performance of two layouts of the platform is evaluated and compared, considering both power generation efficiency and residual volume ratio as key indicators. The results show that the FWT–Net cage integrated platform exhibits superior hydrodynamic stability, characterized by reduced surge and pitch motions, lower mooring force fluctuations, and a higher residual cage volume. Additionally, the platform achieves better power generation efficiency and a higher residual volume ratio, indicating more effective use of the aquaculture space. Based on these findings, an improved integrated design incorporating additional outer net cages is proposed. This design demonstrates enhanced aquaculture capacity while maintaining power generation. The results provide valuable insights for the design of FWT–Net cage integration, promoting the efficient and sustainable utilization of marine space.

Mechanisms of 1-methylcyclopropene (1-MCP) in regulating ethylene signal transduction and its role in stress responses: A review - ShiMing Guo; KaiYi Xue; ShaoYan Si; JianWen Gu; Li Liu; WeiLan Yan; Ang Zhang; PengFei Ren; Xin Du (Plant Science, 2026)

Ecological risk and source apportionment of heavy metals in surface sediments from a key shellfish production area in Northern Liaodong Bay, China - Ang Li; Suyan Xue; Muzhan Sun; Qingbin Ma; Jiaqi Li; Lulei Liu; Ling Zhu; Yuze Mao (Marine Environmental Research, 2026)

Metagenomic insights into diet-mediated gut microbial plasticity and functional adaptations in the tobacco beetle Lasioderma serricorne (Coleoptera: Ptinidae) - Junaid Zafar; Shuhao Zhang; Zhanpeng Zhu; Ziling Wan; Yanqing Li; Ang Li; Ling Huang; Xuewei Zhang; Chen Peng; Shuai Zhong; Fengliang Jin; Xiaoxia Xu (Journal of Stored Products Research, 2026)

Effects of host switching on population rejuvenation and transgenerational fitness in the parasitoid wasp Habrobracon hebetor - Yao Huang; Jintao Wen; Chunlin Tian; Ang Li; Xu Yang; Guowei Li; Siqing Jiang; Yi Mao; Maofa Yang (Journal of Stored Products Research, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

N-halamine-grafted MIL-125-NH2(Ti) as a long-lasting chlorine reservoir for round-the-clock decontamination of Aspergillus aerosols - Ruirui Hou; Hao Yang; Fengming Hou; Yihang Li; Zhipeng Guo; Jin Li; Wei Wei; Ang Wei (Chemical Engineering Journal, 2026)

Design of functional hydrogel beads based on polysaccharide-encapsulated Ganoderma lucidum spores for stability and targeted gastrointestinal delivery of protein–spore complex - Longqin Li; Ang Ma; Jiang Ni; Ruixing Chen; Junzhe Zhang; Zipeng Gong; Hai-Ning Lyu (Carbohydrate Polymers, 2026)

Preparation and Adsorption Performance of Composite Activated Carbon from Organic Sludge and Biomass - Suqing Lu; Ang Wang; Yin Li; Yanqin Guo; Hanqiao Liu (Water, Air, & Soil Pollution, 2026)

Migration of the post-middle holocene mud depocenter off the Zhejiang coast around 2 ka and its controlling mechanism - Jiandong Qiu; Jian Liu; Rongrong Cheng; Yoshiki Saito; Ang Li; Ke Cao; Yuan Tian; Bin Chen; Zhe Xu; Meina Li (Geo-Marine Letters, 2026)

Contamination of commercial 15 N 2 : potential impacts on nitrogen fixation assays and a simple method for quantification - Benjamin T. Uveges; Kimberlee L. Sparks; Warren S. Ang; Hannah Monti; Fay-Wei Li; Jed P. Sparks (Isotopes in Environmental and Health Studies, 2026)

Reply to Wang, L.; Fan, B. Golden Pompano in China Is Trachinotus anak, Not T. ovatus. Comment on “Li et al. DNA Barcode and Correct Scientific Name of Golden Pompano, an Important Marine Aquaculture Fish Species in China. Fishes 2025, 10, 129” - Ang Li; Changting An; Huan Wang; Shuai Che; Shufang Liu; Zhimeng Zhuang (Fishes, 2026)
In a recent study [...]

Unlocking microbial synergy in microalgae-bacteria granules: RSM-driven optimization and lifecycle microbial metagenomics for high-ammonia wastewater treatment - Yanni Geng; Chun-Ang Lian; Liming Yang; Spyros G. Pavlostathis; Xuejiao Qiao; Zhiguang Qiu; Yu Wang; Nan Dong; Anjie Li; Xubiao Luo; Ke Yu (Water Research, 2026)

Effect of seasonal variability on aerobic biostabilisation kinetics of mechanically pre-treated organic fraction municipal solid waste - Vladimir Mironov; Egor Barvashov; Shenghua Zhang; Sofia Telegina; Ang Li (Waste Management, 2026)

Corrigendum to “Mechanisms, pathological features, and intervention strategies for nitrogen mustard-induced skin toxicity” [Toxicol. Lett. 416 (2026) 111815] - Bing Zhu; Guanchao Mao; Qinghe Meng; Ang Li; Chaoying Jin; Yuchong Wang; Xinwei Wang; Wenjun Xue; Fangzhen Hou; Junjie Yang; Qingqiang Xu; Chunyu Xue; et al. (Toxicology Letters, 2026)

Mechanisms, pathological features, and intervention strategies for nitrogen mustard-induced skin toxicity - Bing Zhu; Guanchao Mao; Qinghe Meng; Ang Li; Chaoying Jin; Yuchong Wang; Xinwei Wang; Wenjun Xue; Fangzhen Hou; Junjie Yang; Qingqiang Xu; Chunyu Xue; et al. (Toxicology Letters, 2026)

Corrigendum to “The adaptability, distribution, ecological function and restoration application of biological soil crusts on metal tailings: A critical review” [Sci. Total Environ. 927 (2024), 172169] - Kejun Liao; Chaoqi Chen; Yan Li; Sijia She; Panpan Wang; Yue Tao; Ang Lv; Xinyue Wang; Lanzhou Chen (Science of The Total Environment, 2026)

Superoxide mediated Mn(II) oxidation of an alkali-tolerant bacterium Pseudorhizobium flavum MXJ-1 - Haixia Pan; Fei Li; Ruiying Zhang; Yu Liu; Jieyi Li; Tongtong Wu; Ang Li; Hao Zhou (Journal of Environmental Sciences, 2026)

Cold-summer and summer-snowfall trends and their impacts on vegetation in a warming Mongolian Plateau - Zhang Chen; Junchen Lv; Hao Jiang; Dongyang Lei; Jianguo Xue; Ang Li; Jianhui Huang (Journal of Arid Environments, 2026)

Active control of autoignition inside prechamber for turbulent jet ignition regulation: An optical investigation - Jinze Li; Zhuohang Li; Yezeng Fan; Tiankui Zhu; Zhan Gao; Fei Ren; Ang Li; Lei Zhu; Zhen Huang (Fuel, 2026)

Gliding arc plasma-driven ammonia decomposition for pure ammonia spark-ignition engine - Yezeng Fan; Tiankui Zhu; Zhuohang Li; Jinze Li; Peibo Gao; Jing Wu; Zhan Gao; Ang Li; Lei Zhu; Zhen Huang (Fuel, 2026)

Phosphorus–carbon nitride hybridization enables spatial co-localization of electrons and reactants for enhancing metal-free nitrogen photofixation - Sankar Das; Jiajia Zhang; Zhi Zhong Ang; Siew Kheng Boong; Li Shiuan Ng; Tharishinny Raja Mogan; Hiang Kwee Lee (Chemical Engineering Journal, 2026)

Functional Roles and Regulatory Factors of Histidine-Related Compounds in Skeletal Muscle Metabolism of Teleosts with Distinct Swimming Strategies - Huan Wang; Jiefeng Li; Ang Li; Changting An; Shuai Che; Shengcong Liu; Shufang Liu; Zhimeng Zhuang (Marine Biotechnology, 2026)

Real-time versus postprocessing IGS combined global TEC maps: examined by Jason-3 altimetry and DORIS observations - Ang Li; Ningbo Wang; Zishen Li; Ang Liu; Yang Li; Liang Wang; Bingcheng Liu (GPS Solutions, 2026)

Determination of multi-GNSS differential code biases with satellite antenna phase center corrections - Ningbo Wang; Yang Li; Zishen Li; Ang Liu; Bingcheng Liu (GPS Solutions, 2026)

An integrated meteorological adaptive simulation-optimization framework for real-time irrigation scheduling considering perfect weather forecasts - Kexin Li; Yanan Jiang; Ang Li; Xiangzhe Tian; Jiatong Lu; Tingting Wei; Jiangfeng Xiangli; Xifeng Huang; Yongmin Li; Shikun Sun (Agricultural Systems, 2026)

Drivers of Deposited Nitrogen Retention and Its Contribution to Carbon Sequestration in Chinese Forests - Geshere Abdisa Gurmesa; Ang Wang; Shanlong Li; Feifei Zhu; Kai Huang; Yihang Duan; Qinggong Mao; Quan Zhi; Ronghua Kang; Per Gundersen; Weixing Zhu; Yunting Fang (Global Change Biology, 2026)
Anthropogenic nitrogen (N) deposition alters forest functioning and their capacity to sequester carbon (C), yet its contribution to the forest C sink depends on N retention and allocation between plant biomass and soil pools. Despite high N deposition across China, the magnitude and drivers of N retention and contribution to forest C sequestration remain unclear due to a lack of systematic regional synthesis. Here, we synthesized data from decades of 15 N tracer experiments spanning boreal to tropical regions of China to quantify the retention of deposited N, distribution among plant and soil pools, and contribution to forest C sequestration. On average, Chinese forests retained ~65% of the deposited N, with about two‐thirds stored in the soil. Total retention and partitioning of N varied with climate, successional stage, and N forms. Soil organic layer retention declined, while mineral soil retention increased along a north–south gradient in mean annual temperature. Chronically N‐saturated and disturbed forests exhibited low plant retention, whereas other forests showed substantial uptake across climate zones. Total ecosystem retention efficiency generally declined from boreal to tropical forests. Across successional stages, retention did not differ significantly; however, primary forests retained more deposited N in mineral soils, whereas plantations favored retention in the organic layer. Stoichiometric scaling indicates that CN response (kg C sequestered per kg deposited N) varies among forest types, ranging from ~7 to 40 kg C kg −1 N, with boreal forests and plantations exhibiting the strongest C response due to greater N limitation. This suggests that over the past decade, N deposition enhanced C sequestration by approximately 0.11 Pg C year −1 , accounting for 20%–30% of China's forest C sink. Overall, these findings advance understanding of the drivers of deposited N retention and its contribution to C sequestration, with implications for predicting forest N and C dynamics under global change.

Combined effects of marine heatwaves and nano-titanium dioxide (nano-TiO₂) on the physiological fitness in the mussel Mytilus coruscus - Bing Liu; Menghong Hu; Li'ang Li; Mojiang Zhang; Xinyue Li; Mohamed H. Abo-Raya; Youji Wang (Marine Pollution Bulletin, 2026)

Impact and assessment of hydraulic rake trawling on benthic communities in Urechis unicinctus aquaculture zones, Laizhou Bay, China - Yuze Tang; Erwann Legrand; Jiaqi Li; Haiqing Wang; Ang Li; Lulei Liu; Zirong Liu; Suyan Xue; Shoutuan Yu; Yuze Mao (Ocean & Coastal Management, 2026)

Unveiling switch coordinating wastewater anaerobic biological treatment: The role of quorum sensing and the potential thrust from signal molecule analogs - Chunyan Li; Wei Wei; Jia Meng; Ang Li (Water Research, 2026)

Diffusion mechanism of shield-synchronous grouting slurry and parameter optimization in water-rich fine sand formations - Yang Song; Ang Li; Zhixin Li; Xin Wang; Hao Li (Transportation Geotechnics, 2026)

Lithium ions protected orbital symmetry enables reversible oxygen redox in layered manganese-based cathodes - Ang Gao; Shiguang Zhang; Xiaohui Rong; Qinghua Zhang; Ting Lin; Yichi Wang; Yujie Chen; Valentina A. Bocharova; Weiguang Lin; Shiyu Wang; Pengxiang Ji; Hongwei Li; et al. (Science Bulletin, 2026)

Isolation, characterization, and anti-neuroinflammatory activity of sesquiterpenoids from Pogostemon esquirolii - Yebi Qin; Xinyan Shao; Yinzheng Xie; Hailin Lu; Kaien Chen; Xi Zheng; Guodong Chen; Lishe Gan; Song Ang; Dongli Li (Phytochemistry, 2026)

Mono(2-ethylhexyl) phthalate activates JNK signaling via TLR4-MD2 binding to induce podocyte injury in chronic kidney disease - Jiajun Jing; Shaohui Liu; Li Yan; Li'e Zhang; Qiuju Liang; Yuting Wen; Xiaofeng Huang; Zijuan Qi; Mingjun Wang; Zi'ang Huang; Sijin Liu; Yunfeng Zou; et al. (Journal of Hazardous Materials, 2026)

Dual single sites of single metal atom and molecule ligand on TiO₂ atomic-scale step to boost photocatalytic CO2 reduction - Yuxin Liu; Yang Wang; Yibo Feng; Peixin Cui; Kaiwen Wang; Zhouhao Zhu; Xiaoyuan Zhou; Liyong Gan; Shengqi Chu; Guangcai Chang; Ang Li; Xiaodong Han; et al. (Chemical Engineering Journal, 2026)

A unified intracellular pH landscape with SITE-pHorin: a quantum-entanglement-enhanced pH probe - Shu-Ang Li; Xiao-Yan Meng; Su Zhang; Ying-Jie Zhang; Run-Zhou Yang; Dian-Dian Wang; Yang Yang; Pei-Pei Liu; Jian-Sheng Kang (Science China Life Sciences, 2026)

Aboveground living plant-based methane production does not dominate methane emissions in terrestrial ecosystems - Zhi-Ping Wang; Luke C. Jeffrey; Josep Barba; Katerina Machacova; Xi-Mei Zhang; Ang Li; Shi-Jie Han (Planta, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Characteristics and controlling factors of stable isotopes in precipitation based on 9-year monitoring data in the monsoon transition zone of the Tibetan Plateau - Wang Shao-yong; Wang Qiao-li; Kang Shi-chang; Ding Yong-jian; Xue Yu-ang; He Xiao-bo (Agricultural and Forest Meteorology, 2026)

The combined effects of aging polylactic acid microplastics and TCPP on the byssus genes of the mussel Mytilus coruscus - Li’ang Li; Dan Hu; Zhen Zhong; James Kar-Hei Fang; Menghong Hu; Yueyong Shang; Youji Wang (Marine Pollution Bulletin, 2025)

ALM-LED: autonomous LiDAR mapping in underground space with Luojia explorer anti-collision drone - Shangzhe Sun; Chi Chen; Bisheng Yang; Yuhang Xu; Leyi Zhao; Yong He; Ang Jin; Liuchun Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Investigation into the mechanism of performance enhancement of solvent-based asphalt induced by microbial digestion - Ying Wang; Junyan Yi; Claudio Lantieri; Ang Li; Zhongshi Pei; Xinman Ai; Wenyi Zhou; Ke Xu; Decheng Feng (Chemical Engineering Journal, 2025)

Boosting the plateau capacity via phosphoric acid cross-linking strategy for phenolic resin-based hard carbon - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Haiyan Liu; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Fully exposed Fe clusters activated with interfacial oxygen vacancy for accelerating catalytic ozonation of electron-deficient 1-adamantanecaboxylic acid through interfacial electronic metal-support interactions - Xuan Qu; Lu Wang; Zhi-Qiang Sun; Ang Li; Jun Ma (Chemical Engineering Journal, 2025)

Biochar-mediated electron transfer in a spinel ferrite catalyst boosts peracetic acid activation for water decontamination - Lu Xia; Xinlan Li; Zhuojun Wei; Ang Liu; Jianqiu Chen; Jingge Shang (Chemical Engineering Journal, 2025)

Acetylated glucomannan-CNT scaffolds with dual-drug release promote hiPSCs-driven cortical regeneration by suppressing inflammation and anoikis - Yue Gao; Wenxi Li; Wanting Lu; Fuqiang Tang; Xian Xiao; Yinggang Li; Jiaxing Huang; Zhiqi Liang; Yuqing Wu; Yanwen Li; Qingjian Zou; Liangxue Lai; et al. (Carbohydrate Polymers, 2025)

Exposure to Aldehydes, Heterocyclic Aromatic Amines and Terpenes With Sex Hormones in U.S. Children and Adolescents: Sex-, Age-Dependent Patterns and Vitamin D Effect Modification - Yayuan Mei; Ang Li; Xinyu Wang; Hui Xu; Guoshuang Feng (Phenomics, 2025)

Wollastonite improves soybean yield without toxic trace elements enrichment - Yanzhi Wang; Ji Chen; Guochen Li; Chao Gong; Ang Wang; Ronghua Kang; Feifei Zhu; Jiaoyue Wang; Chang Liu; Dong Liu; Chenxia Su; Quanping Zhang; et al. (Nutrient Cycling in Agroecosystems, 2025)

A non-invasive continuous glucose monitoring method based on the Bergman minimal model - Ang Li; Long Zhao; Chenyang Wu; Zhanxiao Geng; Lihui Yang; Fei Tang (Medical & Biological Engineering & Computing, 2025)

Application and challenges of machine learning in microbial remediation: A review of current status and future directions - Yueyan Zhang; Jun Sasaki; Ang Li; Jundong Chen (Critical Reviews in Environmental Science and Technology, 2025)

Cyanoalanine Synthase encoding gene SlCAS1 regulates tomato fruit ripening by modulating pigment metabolism and ethylene biosynthesis - Song-Li Han; Yu-Qi Zhao; Li-Xia Li; Pedro Garcia-Caparros; Yan-Hong Li; Zhen Wang; Yi-Ang Feng; Kang-Di Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Development and characterization of magnetic cellulose adsorbents functionalized with polyacrylic acid - Chengmin Hou; Zi'’ang Zhao; Fanglin Li; Yuan Bai; Chuangchuang Ren; Chenyu Li; Ze Fan; Wanting Jia; Ying Zhang; Weimin Yan; Yuru Li; Yiting Yang; et al. (Journal of Water Process Engineering, 2025)

Higher ammonia oxidizing activity of comammox cooperates with ammonia-oxidizing bacteria to release N2O in river ecological restoration areas - Yuantao Wang; Shenghua Zhang; Rui Jia; Xin He; Ang Li; Dongdan Yuan (Journal of Environmental Management, 2025)

Metals and polycyclic aromatic hydrocarbons co-exposure: Amino acid omics insights on blood glucose homeostasis - Jiaxin Zhao; Ming Yang; Xiaoqing Xing; Yayuan Mei; Quan Zhou; Meiduo Zhao; Jing Xu; Yanbing Li; Kai Li; Qun Xu; Ang Li (Journal of Environmental Sciences, 2025)

Integrin α5 is involved in immune defense by regulating hemocyte phagocytosis in shrimp - Lingling Li; Bangping Hu; Zi-ang Wang; Jiefeng Gao; Shaoping Weng; Jianguo He; Xiaopeng Xu; Hongliang Zuo (Fish & Shellfish Immunology, 2025)

Effects of Per- and polyfluoroalkyl substances on atherosclerosis: an evidence-based risk assessment in the context of the TRAEC strategy - Yiming Zhu; Zhenzhen Tan; Ziwen An; Longfei Li; Mingmei Guo; Wenjing Duan; Zhixia Yu; Ziang Chen; Yi Liu; Ang Li; Huicai Guo (Environmental Research, 2025)

Sand encased by fine-grained sediment regulates methane migration through the gas hydrate stability zone - Jiliang Wang; Ang Li; Wei Zhang; Jin Sun; Jiecheng Zhang; Xueqing Zhou; Shiguo Wu (Earth and Planetary Science Letters, 2025)

Supersaturation mechanisms and regulation strategies in nucleation-induced crystallization for high-purity fluoride recovery from photovoltaic wastewater - Zhihao Fu; Yadong Wang; Xuan Shi; Danheng Zhou; Zhilin Li; Pengkang Jin; Kunhao Li; Guohua Zhang; Ang Mei; Bingjie Sun; Yun Zhang (Chemical Engineering Journal, 2025)

Unveiling critical drivers of soil salinity prediction accuracy in remote sensing: a global meta-analysis - Zi’ang Cui; Ruiqi Zhang; Wenhui Wang; Zhaoce Peng; Yifan Wu; Ziyue Zhao; Mohan Li; Yutong Cong; Shaoyan Zhang; Zhenhai Li; Lijing Han; Jianli Ding (Plant and Soil, 2025)

Weathering modulates soil microbial biodiversity in a Sygera Mountain alpine forest, Tibetan Plateau - Hongzhe Jiao; Qiuyu Chen; Bin Niu; Xiaoqin Yang; Guiyao Zhou; Ang Hu; Jian Wang; Guicai Si; Jiangrong Li; Eryuan Liang; Manuel Delgado-Baquerizo; Gengxin Zhang (Applied Soil Ecology, 2025)

Scale-factor-based regional zenith tropospheric delay modeling for real-time precise point positioning - Hao Chen; Ningbo Wang; Zishen Li; Kefei Zhang; Suqin Wu; Peng Sun; Ang Liu; Gongwei Xiao (Advances in Space Research, 2025)

Prevalence and genetic analysis of porcine circovirus type 3 (PCV3) in Henan Province of China during 2022-2024 - Lin-Lin Chen; Hao Li; Xuan-Ang Wang; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Archives of Virology, 2025)

Increasing alkalinity to mitigate biogenic acidification and its negative effects during the North–south-relay transportation of abalone - Jiamin Li; Jiaqi Li; Yitao Zhang; Minghui Jiao; Ang Li; Zirong Liu; Zhongzhi Shen; Suyan Xue; Lulei Liu; Yuze Mao (Aquaculture International, 2025)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

A new drag model for staggered cylinders in the oscillating flow: Coupling sheltering and blockage effects - Siyu Li; Ang Li; Ruipeng Li; Dixia Fan (Ocean Engineering, 2025)

Experimental investigation on wave attenuation capacity of kelp farms - Yushun Lian; Jiantao Ma; Dong-ang Li; Jinhai Zheng; Aifeng Tao; Wenxing Chen; Jisheng Zhang; Solomon C. Yim (Ocean Engineering, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

Impacts of synoptic weather patterns on Hefei's ozone in warm season and analysis of transport pathways during extreme pollution events - Feng Hu; Pinhua Xie; Jin Xu; Ang Li; Yinsheng Lv; Zhidong Zhang; Jiangyi Zheng; Xin Tian (Journal of Environmental Sciences, 2025)

Microplastic accumulation in four commercial fish from fish market: Implications for human dietary risk assessment - Renkang Jin; Li'ang Li; Shixiu Wang; Menghong Hu; Wei Huang; Youji Wang (Food Control, 2025)

Impact of per- and polyfluoroalkyl substances exposure on renal dysfunction: Integrating epidemiological evidence with mechanistic insights - Weitao Su; Ziwen An; Yayuan Mei; Zhenzhen Tan; Zexuan Jiang; Xiuli Zeng; Zhiqiang Dong; Ming Yang; Jingtao Wu; Huicai Guo; Ang Li (Environmental Pollution, 2025)

Temporal dynamics of gonadal development and reproduction of wild Manila clam (Ruditapes philippinarum) in the Xiaoqing River estuary, Laizhou Bay - Lulei Liu; Suyan Xue; Ang Li; Yushui Ren; Ling Zhu; Jiaqi Li; Longzhen Liu; Yuze Tang; Yanguo Qiu; Yuze Mao (Estuarine, Coastal and Shelf Science, 2025)

Rational design of SnO2 quantum dots/SnS2 hybrids for enhanced NO2 sensing at room temperature: Insights from DFT and in-situ DRIFTS - Jinzhou Bai; Yanbai Shen; Ang Li; Meili Wu; Siyao Liu; Wenbao Liu; Qiang Zhao; Sikai Zhao; Fanli Meng (Chemical Engineering Journal, 2025)

Monochalcogenide-based retina-inspired photosynapses for energy-efficient neuromorphic computing and artificial visual system application - Muhammad Riaz; Zeesham Abbas; Jiayi Li; Syed Khizar Abbas Abidi; Muhammad Hussain; Syed Hassan Abbas Jaffery; Muhammad Suleman; Haider Abbas; Diing Shenp Ang; Sajjad Hussain; Jongwan Jung (Chemical Engineering Journal, 2025)

Bidirectional regulation of aerobic granular sludge through diffusible signal factor/bis(3′-5′)-cyclic dimeric guanosine monophosphate crosstalk: Restoring stability and enhancing maturation at low temperatures - Chunyan Li; Aiqi Tang; Shenghua Zhang; Vladimir Mironov; Ang Li (Bioresource Technology, 2025)

Hierarchical micro/mesopore-enriched, extra-high surface area activated carbon from coffee grounds for enhanced performance in electrical double layer capacitors - Ying-Hsuan Liu; Hamed Pourzolfaghar; Tai Le -Thanh; Amornrat Srithongpusakul; Gavin Pomoung; Apisara Kittipoomwong; Jia-Qing Liao; Ang-You Hsieh; Yuan-Yao Li (Biomass and Bioenergy, 2025)

Pediatric inflammatory bowel disease in mother-child pairs: clinical risk factors and gut microbiota characteristics - Cunzheng Zhang; Ruqiao Duan; Nini Dai; Yuzhu Chen; Gaonan Li; Xiao’ang Li; Xiaolin Ji; Xuemei Zhong; Zailing Li; Liping Duan (Journal of Zhejiang University-SCIENCE B, 2025)

Ionospheric TEC prediction using the non-stationary inverted transformer fusion model and its performance in Chinese region - Ang Li; Xuefen Zhu; Mengying Lin; Gangyi Tu; Zhe Yan (GPS Solutions, 2025)

Molecular characterization of porcine reproductive and respiratory syndrome virus in Henan and Shanxi, China, during 2023–2024 - Tao Wang; Xuan-Ang Wang; Jia-Qi Zhang; Lan-Lan Zheng; Ping-Li Wang; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

Implications of the UN declaration on the rights of peasants on the operability of the IFC's performance standard on involuntary land acquisition and resettlement - John R. Owen; Deanna Kemp; Julia Loginova; Michelle Li Ern Ang (The Extractive Industries and Society, 2025)

Synergistic experimental-numerical investigation of performance optimization and dynamic behavior in perforated electrode electrocoagulation systems for emulsified oil wastewater remediation - Ang Li; Bing Wang; Meng Yao; Zhilin Ran; Zheng Ju; Ting Chen (Process Safety and Environmental Protection, 2025)

Intestinal microbiota responses to environmental microbiomes and factors across populations of the Manila clam Ruditapes philippinarum - Longzhen Liu; Lulei Liu; Haonan Zhuang; Ang Li; Zirong Liu; Minghui Jiao; Jiamin Li; Suyan Xue; Jiaqi Li; Yushui Ren; Yuze Mao (Marine Environmental Research, 2025)

Femtosecond laser-induced myocardial incision: Preclinical study towards new tools for precision cardiac surgery - Ang Liu; Tong Xia; Siyuan Cao; He Zhao; Yubin Hou; Xuejing Duan; Li Li; Ke Wang; Pu Wang; Chaowu Yan (Journal of Photochemistry and Photobiology B: Biology, 2025)

Standing at the crossroads: How does amino acids function in the crosstalk between pancreas and the kidney under exposure to per- and polyfluoroalkyl substances? - Ming Yang; Ziwen An; Xiaoqing Xing; Yayuan Mei; Haoran Li; Jiaxin Zhao; Zhenzhen Tan; Yanbing Li; Jingjing Zhao; Jiayin Zhao; Meiduo Zhao; Jing Xu; et al. (Journal of Hazardous Materials, 2025)

Molecular and physiological insights into nicotine degradation by Pseudomonas alloputida Pa_12: Implications for environmental management and tobacco processing - Ang Li; Jie Zhang; Ao Li; Junaid Zafar; Ziling Wan; Yanqing Li; Rui Pang; Fengliang Jin; Xiaoxia Xu (Journal of Cleaner Production, 2025)

Effect of PFAS serum exposure pattern on the lipid metabolism: Time to step-forward in causal inference in epidemiology - Ming Yang; Ang Li; Yayuan Mei; Haoran Li; Ziwen An; Quan Zhou; Jiaxin Zhao; Yanbing Li; Kai Li; Meiduo Zhao; Jing Xu; Huicai Guo; et al. (Journal of Environmental Sciences, 2025)

Association between per- and polyfluoroalkyl substances with serum hepatobiliary system function biomarkers in patients with acute coronary syndrome - Fang Xiao; Ming Yang; Junli Lv; Jing Li; Mingmei Guo; WenJing Duan; Haoran Li; Ziwen An; Zhengyi Su; Ang Li; Yi Liu; Jingchao Lu; et al. (Journal of Environmental Sciences, 2025)

Transmission of ultrasonic wave across moisture rocks: Effects of moisture sorption on velocity variation and attenuation - Ang Liu; Guijie Sang; Shimin Liu; Xing Li; Gang Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Impact of C-8 hydroxylation and C-7 methylglucosylation of dihydroquercetin on glucose metabolism in diabetic zebrafish larvae - Yong Cheng; Beijun Ang; Dandan Ma; Zhiwei Li; Fengxian Guo; Zhaojun Wang; Qiuming Chen; Maomao Zeng; Jie Chen; Benu Adhikari; Liduan Yin; Tong Wang; et al. (Food Bioscience, 2025)

Quantifying graphitic curvature and engineering closed pores in phenolic resin hard carbons for enhanced plateau capacity in sodium-ion batteries - Xiaotian Li; Jiapeng Zhang; Renlu Yuan; Boyang Zhao; Chuang Qiu; Dengke Wang; Man Yuan; Ang Li; Haiyan Liu; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Revealing the ionic storage mechanisms of Mo2VC2Tz (MXene) in multiple aqueous electrolytes for high-performance supercapacitors - Xiaodie Xuan; Yangyang Xie; Yi Tang; Jianghong Zhou; Zhao Bi; Junhui Zou; Yu-ang Lei; Jiahang Gao; Lu Li; Aibo Zhang; Chenhui Yang (Chemical Engineering Journal, 2025)

Making Restoration Effective for Dynamic Coastal Wetlands - Qiang He; Zu'ang Li; Chris S. Elphick; Yizhou Sun; William J. Sutherland; Nigel G. Taylor; Kerstin Wasson (Global Change Biology, 2025)
To halt and reverse the trends of ecosystem loss and degradation under global change, nations globally are promoting ecosystem restoration. Restoration is particularly crucial to coastal wetlands (including tidal marshes, mangrove forests, and tidal flats), which are among the most important ecosystems on Earth but have been severely depleted and degraded. In this review, we explore the question of how to make restoration more effective for coastal wetlands in light of the often‐overlooked dynamic nature of these transitional ecosystems between land and ocean. Currently, restoration efforts have focused on removing anthropogenic threats, habitat reconstruction, and planting foundation species, often with mixed success and high costs. The challenges largely lie in the abiotic and biotic dynamics of these transitional ecosystems, including (i) fluctuating environmental stresses, (ii) variable trophic and nontrophic species interactions, (iii) changing connectivity with adjacent land, sea, and freshwater systems, and (iv) accelerating climate change, including sea level rise, droughts, and storms. Future restoration should explicitly account for these abiotic and biotic dynamics from threat removal to habitat reconstruction, assisted succession, and post‐restoration management. We highlight novel yet practical measures to enhance success. In the coming decades, bending the curve of coastal wetland loss and degradation globally also requires better understanding of the abiotic and biotic dynamics of these transitional ecosystems prone to change, using this understanding to develop innovative restoration approaches, and applying new approaches to upscale restoration in synergy with socioeconomic development. Critical to these efforts are collaborations among ecologists, policymakers, business investors, restoration practitioners, and the many millions of people dependent on coastal wetlands.

Two new alkamides and a new polyacetylene glucoside from Achillea alpina L. - Ang Li; Xiu-Wei Li; Huan Guo; Qiang Guo; Xia Wu; Xiao-Qing Chen (Phytochemistry Letters, 2025)

Nickel-doped ZIF-L as a high-performance catalyst for peroxymonosulfate activation and singlet oxygen-mediated As(III) removal - Jian Ye; Chuang Li; Zhiming Yang; Xuan Hu; Qiang Chen; Ang Sun; Mingyang Dai; Shaobo Liu; Chunping Yang (Journal of Environmental Chemical Engineering, 2025)

Anti-aging effect of tea and its phytochemicals - Huijun Liang; Mei Qu; Song Ang; Dongli Li; Chengwei He (Food Research International, 2025)

Variability of urinary metal in short-, mid-, long-term periods and its optimal sampling strategy: A novel epidemiological insight to exposure classification - Yanbing Li; Liu Liu; Yayuan Mei; Jiaxin Zhao; Quan Zhou; Kai Li; Ming Yang; Lingli Sun; Ang Li; Qun Xu (Environmental Research, 2025)

Sulfur-bonded hard carbon with enhanced interfacial and bulk kinetics for potassium-ion hybrid capacitors - Chuang Qiu; Anuj Kumar; Mohammad Tabish; Xinzhuo Mai; Liewen Guo; Ying Zhao; Yibo Zhu; Ang Li; Ghulam Yasin; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

A patient-friendly sprayable rapid gelation powder (SRGP) with prolonged mucoadhesion for oral ulcer therapy - Jingyi Liu; Songbai Zhang; Jinteng Feng; Zhe Feng; Min Zhang; Ang Li; Feng Xu; Haoyu Wang; Dandan Pei; Yuanbo Jia (Chemical Engineering Journal, 2025)

Multi-focus Imaging Under Complex Surface and Structure - Liyan Zhang; Ang Li (Pure and Applied Geophysics, 2025)

Ocean acidification shifts carbonate chemistry heterogeneity in molluscan respiratory microenvironments - Minghui Jiao; Jiaqi Li; Meng Zhang; Jiamin Li; Zibing Hao; Haonan Zhuang; Yujia Zhou; Ang Li; Longzhen Liu; Suyan Xue; Lulei Liu; Yuze Mao (Marine Pollution Bulletin, 2025)

Unraveling the mechanism of fouling mitigation in AGS-MBR system: From AGS properties to foulant interactions - Yu Jiang; Si Wang; Chaoyu Li; Yu-Ang Cai; Xiuquan Xiong; Yinghao Tang; Senlin Shao; Chuansheng Wang; How Yong Ng (Water Research, 2025)

Development and identification of porcine monoclonal antibodies against PEDV from single B cells - Xuan-ang Wang; Hong-xuan Li; Lan-Lan Zheng; Shi-jie Ma; Ping-Li Wang; Li Zhao; Hong-Ying Chen (Veterinary Immunology and Immunopathology, 2025)

The PpAHL17-PpHYH module is involved in light-independent anthocyanin accumulation in fruit peel of Prunus persica - Xiaoyu Zhang; Shihang Sun; Xin Liu; Junren Meng; Mingzhu Yuan; Ang Li; Wenyi Duan; Lei Pan; Zhiqiang Wang; Wenfang Zeng; Liang Niu (Plant Cell Reports, 2025)

Ketamine Alters Specific Gene Expression Profiles by Transcriptome-Wide Responses in a Ketamine-Induced Schizophrenia-Like Mouse Model - Zhe Du; Xiu-mei Zhu; Peng Lv; Ying Pan; Xi-kai Hou; Ang Li; Dong Zhao; Jia-xin Xing; Jun Yao (Molecular Neurobiology, 2025)

Multiplex quantitative PCR assay for porcine circoviruses 2 and 3 and its application for measuring infection rates at different stages of pig production - Zhen Li; Shuaiyin Guan; Jiaying Zhao; Yuhuan Chen; Yang Han; Ang Tian; Saisai Zhou; Huanchun Chen; Yunfeng Song (Archives of Virology, 2025)

Mg/Ca and Sr/Ca ratios of Limnocythere inopinata ostracod valves from the Badain Jaran Desert, Northwest China and their implications for paleoenvironmental reconstruction - Gaolei Jiang; Linjing Liu; Xin Mao; Zhongshuang Cheng; Zhe Wang; Meng Li; Nai'’ang Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Study on short-term total hardness prediction of water quality based on CNN-BiLSTM-SA model: A case study of Henan Province - Huan Xu; Hehu Zhang; Youwei Wang; Lingling Lu; Ang Wu; Ying Chen; Yahui Li; Chuanxin Dong; Xiushan Wang (Journal of Water Process Engineering, 2025)

Zinc oxide nanoparticles promote migrasomes formation - Ang Li; Chengxiong Yang; Leiliang Zhang (Journal of Hazardous Materials, 2025)

Degradation of o-DCB and dioxins by MnCe catalysts prepared via the mechanochemical method - Fan Yao; Yaqi Peng; Zhiyuan Gong; Ling Wang; Hongxian Li; Qi Liu; Guanjie Wang; Minghui Tang; Ang Cao; Shengyong Lu (Journal of Environmental Chemical Engineering, 2025)

Inorganic and organic constituent analysis: A data fusion strategy to differentiate between wines of different origins - Yingyue Su; Zhaoxiang Wang; Qianqian Liu; Yuyu Li; Cui Zhang; Xiaohui Feng; Ang Zhang; Chunlong Yuan (Food Control, 2025)

Experimental study of thermal comfort by variable temperature and velocity air supply system in operating room - Bin Zhou; Ang Wang; Hui Ren; Jie Xia; Fan Peng; Shao-Cong Wang; Yi-Chu Wang; Hao-Yi Zhao; Wen-Jie Li; Mei-Lan Tan; Risto Kosonen (Building and Environment, 2025)

Cohort Profile: Precision Environmental Health Cohort of Healthy Undergraduates - Yanbing Li; Yayuan Mei; Jiaxin Zhao; Quan Zhou; Kai Li; Ming Yang; Liu Liu; Huicai Guo; Qun Xu; Ang Li (Phenomics, 2025)

Intensive rotational grazing has positive effects on productivity of rangeland - Ping Ge; Jianguo Xue; Yaqian Ru; Yulin Li; Dongxu Li; Peng Han; Ang Li; Jianhui Huang (Agriculture, Ecosystems & Environment, 2025)

Biological functions and molecular mechanisms of circHIPK3 in digestive system tumors - Jian Li; Xin Su; Xiao Xu; Youbao Ye; Cailiu Wang; Ang Liu; Changchun Zhao; Wenxiu Liu; Liwen Yang; Tao Wang; Xiangyong Hao (Human Cell, 2025)

Intelligent real-time status identification for anti-roll tank via solid-liquid triboelectric nanogenerators - Xing'ang Xu; Hao Wu; Zhongjie Li; Siyu Jia; Shuaitao Jin (Ocean Engineering, 2025)

Comparative analysis of femtosecond, picosecond, and nanosecond laser techniques for transseptal puncture: An in vitro study with pathological correlation - Ang Liu; Tong Xia; Siyuan Cao; He Zhao; Yubin Hou; Xuejing Duan; Li Li; Ke Wang; Pu Wang; Chaowu Yan (Journal of Photochemistry and Photobiology B: Biology, 2025)

Progressing towards eco-friendly agricultural management: Utilizing Ginkgo biloba leaf litter for potato common scab control - Shoudong Wang; Ji-Ang Nie; Jiguang Wang; Minghao Lv; Qingquan Li; Mingcong Li; Bo Zhou; Zheng Gao; Wenchong Shi (Journal of Environmental Management, 2025)

MAX-DOAS observations of pollutant distribution and transboundary transport in typical regions of China - Hongmei Ren; Ang Li; Zhaokun Hu; Hairong Zhang; Jiangman Xu; Xinyan Yang; Jinji Ma; Shuai Wang (Journal of Environmental Sciences, 2025)

Spatial-temporal distribution and emission of urban scale air pollutants in Hefei based on Mobile-DOAS - Zhidong Zhang; Pinhua Xie; Ang Li; Min Qin; Jin Xu; Zhaokun Hu; Xin Tian; Feng Hu; Yinsheng Lv; Jiangyi Zheng; Youtao Li (Journal of Environmental Sciences, 2025)

Dynamic interactions between Fe, Mn, S and C cycles in the Okinawa Trough seep sediments - Cuiling Xu; Qing Li; Taiheng Lv; Zhilei Sun; Ang Li; Ye Chen; Xilin Zhang; Feng Cai; Nengyou Wu (Global and Planetary Change, 2025)

Probing the microwave induced overheating at electrode surface using a combined electrochemical and fluorescence method - Zongliang Kou; Zhenyu Zhao; Hong Li; Ang Li; Kai Liu; Xiaolei Fan; Xin Gao (Chemical Engineering Journal, 2025)

Spatial configuration engineering of phenolic resins to tune the closed pores of hard carbon for enhanced plateau-capacity sodium storage - Liewen Guo; Chuang Qiu; Haiyan Liu; Renlu Yuan; Xiaotian Li; Xin Li; Kairan Li; Wanxiong Zhu; Mohammad Tabish; Xuewei Liu; Ang Li; Xiaohong Chen; et al. (Chemical Engineering Journal, 2025)

Investigation of the synergistic effects of reaction-diffusion processes in hierarchical macro-mesoporous electrodes of solid oxide fuel cells - Mingyuan Sun; Ang Li; Xuejie Zhang; Yuxuan Fei; Lei Zhu; Zhen Huang (Chemical Engineering Journal, 2025)

High content of single-atomic sulfur in nano carbon spheres boosting potassium storage performance - Bin Cao; Zirong Guo; Huan Liu; Yu Ma; Wei Zhao; Yiheng Yang; Ang Li; Huaihe Song; Yaxiong Yang; Zhenglong Li; Wubin Du (Chemical Engineering Journal, 2025)

Active wildfire detection via satellite imagery and machine learning: an empirical investigation of Australian wildfires - Harikesh Singh; Li-Minn Ang; Sanjeev Kumar Srivastava (Natural Hazards, 2025)
Forests worldwide play a critical role in biodiversity conservation and climate regulation, yet they face unprecedented challenges, particularly from wildfires. Early wildfire detection is essential for preventing rapid spread, protecting lives, ecosystems, and economies, and mitigating climate change impacts. Traditional wildfire detection methods relying on human surveillance are limited in scope and efficiency. However, advancements in remote sensing technologies offer new opportunities for more efficient and comprehensive detection. This study highlights the integration of satellite sensors, capable of detecting thermal anomalies, smoke plumes, and vegetation health changes, with machine learning, particularly Support Vector Machines (SVMs), to enhance detection efficiency and accuracy. These algorithms analyse satellite data to identify fire patterns and provide near real-time alerts. SVMs’ adaptability over time improves performance, making them suitable for evolving fire regimes influenced by climate change. Focusing on the Wolgan Valley in Eastern Australia, the study utilised Landsat-8 imagery and SVMs to detect active fires and classify burned areas. Results demonstrated that combining various spectral bands, such as the Shortwave Infrared (SWIR) and Near-Infrared (NIR), enhances the identification of active fires and smoke. The introduction of the Normalized Difference Fire Index (NDFI) further refines detection capabilities by leveraging distinct spectral characteristics from Landsat 8 imagery. Despite the promise of these technologies, challenges such as data availability and model interpretability remain. Future research should focus on integrating diverse data sources, advancing machine learning techniques, developing real-time monitoring systems, addressing model interpretability, integrating unmanned aerial vehicles, and considering climate change impacts. This study underscores the potential of machine learning algorithms and innovative indices like NDFI to improve wildfire detection and management strategies, ultimately enhancing our ability to protect lives and ecosystems in fire-prone regions.

Investigations of spatial-temporal distribution and regional transport in typical section of NO2 in eastern China using Mobile-DOAS - Zhidong Zhang; Pinhua Xie; Ang Li; Jin Xu; Xin Tian; Feng Hu; Zhaokun Hu; Yinsheng Lv; Youtao Li; Qiang Zhang; Wenqing Liu (Science of The Total Environment, 2025)

Study on the genesis of carbonate cements in tight and non-tight sandstone reservoirs in Fukang Sag - Li Na; Wang Zi'ang; Liu Gang; Wang Guozhi; Huang Sheng; Liu Jinlong; Jing Yang; Chen Haixia (Ore and Energy Resource Geology, 2025)

Role of per- and polyfluoroalkyl substances in the cardiorenal system: Unraveling crosstalk from the network of pollutants and phenotypes - Ming Yang; Jiaxin Zhao; Ziwen An; Haoran Li; Chaoying Ma; Junli Lv; Fang Xiao; Zhenzhen Tan; Longfei Li; Xiaoguang Zhang; Xuehui Liu; Yi Liu; et al. (Journal of Environmental Sciences, 2025)

High-Voltage aqueous supercapacitors based on l-lysine pH Self-Buffering Coating-modified carbon cloth electrode - Ang Xu; Jie Gao; Huan Li; Xiyu Song; Bo Xu; Ying Liu; Yuanyuan Yu; Ping Wang; Qiang Wang; Man Zhou (Chemical Engineering Journal, 2025)

Peroxisomal biogenesis factor 11 as a novel target to trigger lipid biosynthesis and salt stress resistance in oleaginous Tetradesmus obliquus - Yunzhuan Xue; Wei Wang; Xiajule Sheng; Zexu Zheng; Zihan Wang; Fangling Ding; Jinjin Li; Zhiwei Sun; Yu’ang Cai; Xianhua Wang; Jiao Xue (Bioresource Technology, 2025)

Quantifying time-evolving droplet velocities and size: Insights from experimental image analysis - Lanyue Zhang; Naseeb Ahmed Siddiqui; Steven Tay; Zhengwei Ge; Hongying Li; Elisa Y.M. Ang; Peng Cheng Wang (Building and Environment, 2025)

Identification of elite alleles associated with glume-opening angle in rice natural population - Yingying Zhao; Hui Jiang; Chunyu Jing; Tianhu Li; Yanan Zhang; Zhengbo Liu; Yinping Chang; Mingyu Du; Hao Sun; Jinghan Sun; Yang Ang; Xianping Cheng; et al. (Euphytica, 2025)

Characterizing PPP ambiguity resolution residuals for precise orbit and clock corrections integrity monitoring - Mingqiang Xie; Ningbo Wang; Ahmed El-mowafy; Zishen Li; Ang Liu; Dongyan Wei (GPS Solutions, 2025)

DNA Barcode and Correct Scientific Name of Golden Pompano, an Important Marine Aquaculture Fish Species in China - Ang Li; Changting An; Huan Wang; Shuai Che; Shufang Liu; Zhimeng Zhuang (Fishes, 2025)
The golden pompano ranks at the top of production in current China’s marine fish aquaculture; however, there has been long-standing controversy regarding its valid scientific name. Multiple latin names were used simultaneously to refer to golden pompano, such as Trachinotus ovatus, T. blochii, T. mookalee and T. anak. Moreover, two distinct morphological species are regarded as deserving the scientific name T. ovatus. In this study, we employed DNA barcoding to determine which particular species the “golden pompano” represents and to explore the potential synonyms and cryptic species within T. ovatus and its closely related species. We analyzed the DNA barcodes of golden pompano samples from various aquaculture farms in China’s main production regions, as well as most species within the genus Trachinotus. The phylogenetic analyses revealed that all T. ovatus sequences clustered into two divergent clades with a large genetic distance, and the two clades were geographically separated, being from the Indo-west Pacific and the East Atlantic regions, respectively. Based on the type locality information and historical distribution records, we support the validity of the naming of Trachinotus ovatus from the Indo-west Pacific, and the so-called Trachinotus ovatus from the East Atlantic may represent a cryptic species. All the golden pompano samples were clustered into the Indo-west Pacific T. ovatus clade, with a considerably small intragroup genetic distance, which suggests that the golden pompano in China should be identified as the species Trachinotus ovatus. The golden pompano, T. blochii and T. mookalee were completely separated into distinct monophyletic clades in the phylogenetic trees, which indicated that they are different species. The T. anak clustered with the monophyletic clade of Indo-west Pacific T. ovatus and the genetic distance between them was at the intraspecific difference level. This implied that the T. anak might be the junior synonym of T. ovatus. The species delimitations based on the ABGD and bPTP methods are in agreement with the findings from phylogenetic analyses. The above results help to form a consistent viewpoint regarding the naming of the golden pompano and provide new understandings for the taxonomy of the genus Trachinotus.

Correction: Exposure to Aldehydes, Heterocyclic Aromatic Amines and Terpenes with Sex Hormones in U.S. Children and Adolescents: Sex-, Age-Dependent Patterns and Vitamin D Effect Modification - Yayuan Mei; Ang Li; Xinyu Wang; Hui Xu; Guoshuang Feng (Phenomics, 2025)

Multi-modal deep learning approaches to semantic segmentation of mining footprints with multispectral satellite imagery - Muhamad Risqi U. Saputra; Irfan Dwiki Bhaswara; Bahrul Ilmi Nasution; Michelle Ang Li Ern; Nur Laily Romadhotul Husna; Tahjudil Witra; Vicky Feliren; John R. Owen; Deanna Kemp; Alex M. Lechner (Remote Sensing of Environment, 2025)

Integrated metabolomic and transcriptomic analysis reveals the regulatory effects of IAA on polyphenol biosynthesis and antioxidant activity in Phlebopus portentosus - Taobo Xiang; Feng Ge; Lei Zhu; Gaige Shao; Tao Wu; Hao Fan; Yueqian Liu; Longyu Wang; Jing Wang; Peng Li; Qin He; Ailiang Jiang; et al. (Food Bioscience, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Wet deposition of atmospheric Hg in a typical inland city in North China: Sources, influencing factors, and health risk assessment - Xiaofei Li; Wen Yang; Fei Gao; Ang Li; Lekhendra Tripathee; Junming Guo; Lang Liu (Environmental Pollution, 2025)

Size effect in shear failure of RC beams reinforced with CFRP sheets: Influences of CFRP adhesion angle and shear-span ratio - Liu Jin; Peng Qin; Jiangxing Zhang; Dong Li; Xuan-ang Jiang; Xiuli Du (Engineering Structures, 2025)

Generation and resource potential of waste PV modules considering technological iteration: A case study in China - Zishuo Wang; Bo Li; Xiaolong Song; Xuning Zhuang; Wenjie Wu; Ang Li (Environmental Impact Assessment Review, 2025)

Mitochondrial biogenesis microcarriers break membrane barriers for endogenous nucleus pulposus repair - Xiaohu Li; Hongze Chang; Libin Pang; Ang Li; Juan Wang; Yi Yu; Honglei Xiao; Zhengwei Cai; Wenguo Cui; Xiaodong Liu (Chemical Engineering Journal, 2025)

CO2 removal with enhanced wollastonite weathering in acidic and calcareous soils - Chenxia Su; Ronghua Kang; Wentao Huang; Ang Wang; Xue Li; Kai Huang; Qiang Zhou; Yunting Fang (Soil Ecology Letters, 2025)

Phellodendrine Exerts Protective Effects on Intra-abdominal Sepsis by Inactivating AKT/NF-kB Signaling - Ang Li; Peng Liu; Jiaohong Gan; Weijun Fang; Anjie Liu (Cell Biochemistry and Biophysics, 2025)

Effects of Ammonia loading and oxygen flux on nitrogen removal in a PNA-coupled MABR - Jiang-Feng Zhang; Jinfeng Bao; Chun-Yu Lai; Chen Zhou; Ang Li; He-Ping Zhao (Journal of Water Process Engineering, 2025)

Tissue accumulation and hepatotoxicity of 8:2 chlorinated polyfluoroalkyl ether sulfonate: A multi-omics analysis deciphering hepatic amino acid metabolic dysregulation in mice - Zhenzhen Tan; Ziwen An; Junli Lv; Fang Xiao; Longfei Li; Jing Li; Wenjing Duan; Mingmei Guo; Xiuli Zeng; Yi Liu; Ang Li; Huicai Guo (Journal of Hazardous Materials, 2025)

Deciphering the code of temperature rise on aerobic granular sludge stability: A DSF-c-di-GMP mediated regulatory mechanism - Aiqi Tang; Chunyan Li; Donglei Feng; Ang Li (Environmental Research, 2025)

MXene-based mild photothermal therapy synergizes STING activation to enhance the efficacy of cancer vaccines post-cryoablation - Fuming Wang; Xiaodong Zhu; Qianwen Zhang; Minghui Xie; Lei He; Jiahao Guo; Ang Li; Qingsong Yang; Jijin Yang; Wei Li (Chemical Engineering Journal, 2025)

Establishment and Characterization of Bisexually Fertile Triploid Dwarf Surf Clam Mulinia lateralis - Ang Zhao; Zujing Yang; Haoran Wang; Hao Wang; Shuai Zhong; Chenhui Li; Yuehuan Zhang; Jingjie Hu; Zhenmin Bao; Xiaoting Huang (Marine Biotechnology, 2025)

Salinity tolerance assessment of different families of the razor clam Sinonovacula constricta using physiological traits - Chen Yihua; Shao Zhengyu; Zhou Guolong; Hu Ang; Ding Hongbing; Li Haoyu; Dong Zhiguo; Niu Donghong; Li Jiale (Aquaculture, 2025)

Analysis of the softening-melting mechanism of cold-bonded briquette from return sinter fines - Ying Li; Dejin Qiu; Manqing Li; Yuandong Xiong; Timo Fabritius; Su Cao; Ang Li; Abdallah Ahmed Elsherbiny; Jie Ren; Han Wei; Yaowei Yu (Journal of Cleaner Production, 2025)

Enhancing fish sludge bioconversion kinetics for nutrient recovery in aquaponics using a modified biological aerated filter with a novel media of polyhedral hollow spheres - Ang Chen; Hong Zhang; Yongxia Zi; Yueshu Gao; Chew Tin Lee; Chunjie Li (Journal of Environmental Management, 2025)

Stratified charge assisted jet ignition mode (SCAJI) for low-speed two-stroke Otto cycle ammonia marine engine - Zhuohang Li; Yezeng Fan; Jinze Li; Kaijian Wu; Zhenyingnan Zhang; Fei Ren; Zhan Gao; Ang Li; Lei Zhu; Zhen Huang (Fuel, 2025)

Breaking separation bottleneck in sucralose production: Clarifying the obscure mechanism and pre-embedding second solvents for highly selective separation of chlorinated product - Xiaoping Chen; Jiayan Lei; Zhoulin Lv; Zi'ang Chen; Shitong Lin; Zhenming Guo; Huadong Luo; Yingshu Wang; Jingjing Chen; Haohong Li; Huidong Zheng (Chemical Engineering Journal, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Methane emissions from the riverine sandy wetlands on the Mongolia Plateau - Ang Li; Zun-Lan Luo; Katerina Machacova; Song Zhao; Jin-Chao Feng; Xing-Guo Han; Zhi-Ping Wang (Environmental Monitoring and Assessment, 2024)

Biogenic amorphous FeOOH activated additional intracellular electron flow pathways for accelerating reductive dechlorination of tetrachloroethylene - Yang Yu; Ang Li; Sheng-Qiang Fan; He-Ping Zhao (Water Research, 2024)

Effect of the LIF gene on the cell cycle and apoptosis of ovarian granulosa cells in white Muscovy ducks - Qing-hua Tao; Ning-ning Sun; Meng-shi Wang; Wan-xin Zhao; Wei Liu; Xu Zhang; Ang Li (Theriogenology, 2024)

Extreme heat event influences the toxic impacts of nano-TiO2 with different crystal structures in mussel Mytilus coruscus - Shuaishuai Wei; Yiran Mao; Inna M. Sokolova; Zhuoqing Li; Li'ang Li; Malik Shahzaib Khalid; Zhihan Tu; Zhen Zhong; Menghong Hu; Youji Wang (Science of The Total Environment, 2024)

Construction of a synthetic anaerobic dechlorination microbiome to degrade chlorinated ethenes by application of metabolic interactions principle - Zeyi Wang; Yang Yu; Rongjian Zhao; Ang Li (Science of The Total Environment, 2024)

Endophytic bacteria in Halogeton glomeratus from mining areas are mainly Sphingomonas pseudosanguinis, with a Cyanobacteria moving from roots to leaves to avoid heavy metals - Xisheng Tai; Ruiqi Yang; Jun Li; Ang Li; Wei Chen; Jiajia Ding (Rhizosphere, 2024)

Salinity impacts on n-alkanes in lake sediments of the Badain Jaran Desert, Northwestern China: Implications for paleoclimate reconstruction - Meng Li; Zhuolun Li; Shipei Dong; Lin Chen; Xianbao Su; Chen'ao Lu; Aifeng Zhou; Nai'ang Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Unique biogenesis and kinetics of hornwort Rubiscos revealed by synthetic biology systems - Zhen Guo Oh; Tanner Ashton Robison; Dan Hong Loh; Warren Shou Leong Ang; Jediael Zheng Ying Ng; Fay-Wei Li; Laura Helen Gunn (Molecular Plant, 2024)

The zinc-finger transcription factor ZFP8 negatively regulates the drought stress response in Arabidopsis thaliana by inhibiting the transcriptional activity of ABF2 - Yu'ang Tian; Yanling Li; Kelan Wang; Ran Xia; Yingru Lin; Guohui Pan; Haoyu Shi; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2024)

Tire microplastic particles and warming inhibit physiological functions of the toxic microalga Alexandrium pacificum - Bole Wang; Dan Qiao; Bin Wen; Li'ang Li; Menghong Hu; Wei Huang; Youji Wang (Journal of Hazardous Materials, 2024)

Legacy and alternative per- and polyfluoroalkyl substances spatiotemporal distribution in China: Human exposure, environmental media, and risk assessment - Jing Li; Wenjing Duan; Ziwen An; Zexuan Jiang; Longfei Li; Mingmei Guo; Zhenzhen Tan; Xiuli Zeng; Xuehui Liu; Yi Liu; Ang Li; Huicai Guo (Journal of Hazardous Materials, 2024)

The effects of corona discharge from a cold plasma source on the physicochemical properties and shelf-life of milk - Tan-Ang Lee; Yi-Hsuan Lin; Po-Hsien Li; Jou-Hsuan Ho (Food Bioscience, 2024)

Physical properties and anisotropy of sandstone during freeze-thaw cycle under unidirectional constraint - Tantan Zhu; Huanhuan Zhu; Ang Li; Xilei Zong; Bin Zeng; Xin He (Cold Regions Science and Technology, 2024)

Rapamycin protects mouse skin from ultraviolet B-induced photodamage by modulating Hspb2-mediated autophagy and apoptosis - Ang Li; Ai-Jun Chen; Jing Xu; Zhu-Yuan Wen; Gen-Long Bai; Zi-Yue Wang; Yu-Xin Jiang; Ping Wang (Molecular Biology Reports, 2024)

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

Study and application of wide-azimuth seismic anisotropy analysis and correction in shale reservoir in Gulong Sag, Songliao Basin, China - Liyan Zhang; Ang Li (Geosciences Journal, 2024)

Cobalt nanoparticles attenuate microplastic-induced vascular endothelial injury via Nrf2 pathway activation - Linhua Deng; Mengjun Li; Zhongjing Jiang; Gang Xiang; Sihan He; Hongqi Zhang; Ang Deng; Yunjia Wang (Science of The Total Environment, 2024)

Disturbed glucose homeostasis and its increased allostatic load in response to individual, joint and fluctuating air pollutants exposure: Evidence from a longitudinal study in prediabetes - Yayuan Mei; Ang Li; Jiaxin Zhao; Yanbing Li; Quan Zhou; Ming Yang; Meiduo Zhao; Jing Xu; Kai Li; Guohuan Yin; Jingtao Wu; Qun Xu (Science of The Total Environment, 2024)

A new strategy optimisation method for underwater flapping foil propulsion based on Twin-Delayed Deep Deterministic and Gaussian process regression - Yinghe Yang; Handi Wei; Dixia Fan; Ang Li (Ocean Engineering, 2024)

Large-scale oyster farming accelerates the removal of dissolved inorganic carbon from seawater in Sanggou Bay - Jiaqi Li; Zengjie Jiang; Meng Zhang; Xin Sun; Minghui Jiao; Jiamin Li; Suyan Xue; Ang Li; Longzhen Liu; Ling Zhu; Yuze Mao (Marine Environmental Research, 2024)

Synthesis of nitrogen-doped crystalline Ga2O3 thin films via trimethylgallium doped NH3/H2/N2/O2 premixed stagnation flames - Lun’ang Li; Shengfeng Luo; Mengzhao Chang; Guanjie Yin; Mingchen Sun; Jingrui Ma; Xiao Wei Sun; Igor Rahinov; Bo Zhou (Fuel, 2024)

Formation mechanism and geophysical properties of fracture-filling gas hydrate in the host sediments: A comprehensive review - Gaowei Hu; Zhun Zhang; Yapeng Zhao; Qingtao Bu; Ang Li; Wengao Zhao; Zihao Wang; Xiaoqian Qiu; Tong Liu; Shengbiao Liu; Wanjun Lu; Nengyou Wu (Earth-Science Reviews, 2024)

Linkage engineered poly(heptazine imide) optimizes charge transfer for efficient photocatalytic H2O2 production: Regulating oxygen reduction pathway - Jianning Gao; Zhipeng Guo; Yihang Li; Bing Yang; Ang Wei (Chemical Engineering Journal, 2024)

Efficient catalysis for acidic methanol oxidation: Exploration of a Low-Platinum quaternary alloy catalyst via a Two-Step method - Shuaiqi Li; Zi'ang Fan; Yulong Li; Yue Zhang; Youxin Zhao; Jingxiang Zhao; Jingjia Zhang; Zhenbo Wang (Chemical Engineering Journal, 2024)

Emerging transition metal sulfide/MXene composites for the application of electrochemical energy storage - Xianghui Hu; Pin Ma; Zehao Zhang; Jian Wang; Cheng Li; Yee Sin Ang; Haibo Li; Hui Ying Yang (Chemical Engineering Journal, 2024)

Boosted photocatalytic H2O2 production in pure water with amino-modified N, S-doped carbon dots - Haoyuan Qin; Lei Sun; Suchang Zou; Ang Bian; Yanhua Cui; Jianhua Hou; Changyu Lu; Chunsheng Li; Feng Guo; Weilong Shi (Chemical Engineering Journal, 2024)

An overview of cellulose aerogels and foams for oil sorption: Preparation, modification, and potential of 3D printing - Ang Li; Tim Huber; David Barker; Ali Reza Nazmi; Hossein Najaf Zadeh (Carbohydrate Polymers, 2024)

Role of diffusible signal factor in regulating aerobic granular sludge formation under temperature shocks - Aiqi Tang; Shengqiang Fan; Ping Zhang; Ang Li (Bioresource Technology, 2024)

Rational regulation of post-electrodialysis electrochromic anion exchange membranes via TiO2@Ag synergistically strengthens visible-light photocatalytic anti-contamination activity - Yuyang Yao; Yueyue Lu; Jingwen Xu; Jiacheng Yu; Liang Guo; Heda Ding; Jian Li; Junbin Liao; Edison Huixiang Ang; Zhenlu Shen; Jiangnan Shen (Water Research, 2024)

Bio-based microplastic polylactic acid exerts the similar toxic effects to traditional petroleum-based microplastic polystyrene in mussels - Zhen Zhong; Wenrui Shang; Peiwen Yang; Shixiu Wang; Liming Chen; Zhaowen Chen; Li’ang Li; Muhammad Faisal Khalil; Menghong Hu; Xiangrong Xu; Youji Wang (Science of The Total Environment, 2024)

Review on recent advances in supported metal catalysts for synthesis of high energy density fuels - Tian Li; Dandan Jia; Shenglan Zhou; Zhiyuan Liu; Juan Chen; Tao Ban; Ang Li; Haijian Li; Hongyi Gao (Fuel, 2024)

Tris(1-chloro-2-propyl) phosphate enhances the adverse effects of biodegradable polylactic acid microplastics on the mussel Mytilus coruscus - Zhen Zhong; Wei Huang; Yiwei Yin; Shixiu Wang; Liming Chen; Zhaowen Chen; Jiacheng Wang; Li'ang Li; Mansoor Khalid; Menghong Hu; Youji Wang (Environmental Pollution, 2024)

Probabilistic evaluation method for the stability of large underground cavern considering the uncertainty of rock mass mechanical parameters: A case study of Baihetan underground powerhouse project - Guofeng Liu; Chi Zhou; Kun Feng; Quan Jiang; Shengfeng Li; Han Bao; Ang Li (Engineering Geology, 2024)

Highly textured CMOS-compatible hexagonal boron nitride-based neuristor for reservoir computing - Haizhong Zhang; Jiayi Li; Xin Ju; Jie Jiang; Jing Wu; Dongzhi Chi; Diing Shenp Ang; Wei Hu; Rongshan Wei; Minmin Zhu; Xiaoqiang Lu (Chemical Engineering Journal, 2024)

Janus-structured colorimetric and fluorescent nanocomposites with highly luminescent retention to enhance point-of-care diagnosis - Xuan-ang Shen; Xirui Chen; Haoxiang Zhou; Song Chen; Jinyu Wu; Xiangmin Li; Xiaolin Huang; Yonghua Xiong (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

The MYB transcription factor PpMYB5 regulates Pp4CL1/Pp4CL2 expression to promote lignin biosynthesis of fruit russeting in the flat nectarine - Yule Miao; Wenyi Duan; Ang Li; Mingzhu Yuan; Junren Meng; Hongmei Wang; Lei Pan; Shihang Sun; Guochao Cui; Caiyun Shi; Liang Niu; Wenfang Zeng (Plant Cell Reports, 2024)

Spermidine protects cartilage from IL-1β-mediated ferroptosis - Qi Cheng; Li Ni; Ang Liu; Xiaoxiong Huang; Pan Xiang; Qin Zhang; Huilin Yang (Molecular and Cellular Biochemistry, 2024)

Association Between Metal Exposure and Mitochondrial DNA Parameters and the Potential Mediation Effect of Oxidative Stress - Jing Xu; Meiduo Zhao; Xiaoyu Ge; Xiaolin Liu; Lanping Wei; Ang Li; Yayuan Mei; Guohuan Yin; Jingtao Wu; Qun Xu (Exposure and Health, 2024)

High-intensity exercise training in large yellow croaker is a compromise between disease resistance and fish welfare - Junjia Zeng; Ang Qu; Yacheng Deng; Pengxin Jiang; Ji Zhao; Jiaying Wang; Yue Liu; Wei Liu; Qiaozhen Ke; Fei Pu; Yaxian Li; Peng Xu (Aquaculture, 2024)

Physiological responses of the microalga Isochrysis galbana exposed to polystyrene microplastics with different particle sizes - Xue'en Jin; Yuyang Fang; Li'ang Li; Menghong Hu; James Kar-Hei Fang; Fahim Ullah Khan; Wei Huang; Youji Wang (Marine Environmental Research, 2024)

Was there an active continental margin arc along the western margin of Zhangguangcailing Terrane in the eastern Central Asian Orogenic Belt? - Zhaoxu Chen; Boran Liu; Qingbin Guan; Yongjiang Liu; A.Yu. Peskov; Sanzhong Li; Qi’ang Fang (Lithos, 2024)

High valent manganese-oxo species activation of peroxymonosulfate by different phases manganese oxides nanoplates for catalytic water decontamination - Ang Li; Bin Li; Li-Ming Sun; Le-Xuan Liu; Chang Liu; Ya-Meng Dong; Xing Zhang (Chemical Engineering Journal, 2024)

Stretchable, adhesive, conductive hydrogel initiated by liquid metal complex for multi-functional sensing - Yuecong Luo; Qiannian Yang; Minzhang Chen; Kaixiang Long; Cuicui Su; Jingxing Li; Mingkun Huang; Ang Lu; Shishang Guo (Chemical Engineering Journal, 2024)

Research on fine modeling of dispersion fuel plate based on lattice method - Yuqing Chen; Pengfei Liu; Song Li; Lei Lou; Ang Li (Annals of Nuclear Energy, 2024)

Associations between co-exposure to per- and polyfluoroalkyl substances and organophosphate esters and erythrogram in Chinese adults - Ziwen An; Yanbing Li; Jing Li; Zexuan Jiang; Wenjing Duan; Mingmei Guo; Yiming Zhu; Xiuli Zeng; Linfeng Wang; Yi Liu; Ang Li; Huicai Guo; et al. (Chemosphere, 2024)

Biogeochemical changes during supercritical CO2–H2O-coal-microorganism interaction - Wenxing Wang; Weiyu Huang; Wancheng Zhu; Shuyuan Liu; Huiqian Yang; Tecai Li; Yanyan Liu; Ang Li (Gas Science and Engineering, 2024)

Efficient synthesis of quaternary piezo-photonic materials for pressure visualization and E-signature anti-counterfeiting - Jiaren Du; Tengyue Wang; Yukun Li; Puxian Xiong; Yao Xiao; Ang Feng; Xiaomeng Wang; Kai Jiang; Hengwei Lin (Chemical Engineering Journal, 2024)

Non-sacrificial additive regulated electrode–electrolyte interface enables long-life, deeply rechargeable aqueous Zn anodes - Ang Li; Xinyu Zhang; Zeyu Xu; Maochun Wu (Chemical Engineering Journal, 2024)

Ultrafast hot electron transfer and trap-state mediated charge separation for boosted photothermal-assisted photocatalytic H2 evolution - Hao Yuan; Haoyuan Qin; Kaiqu Sun; Xinhai Sun; Jialin Lu; Ang Bian; Jianhua Hou; Changyu Lu; Chunsheng Li; Feng Guo; Weilong Shi (Chemical Engineering Journal, 2024)

Mo4/3B2Tx induced hierarchical structure and rapid reaction dynamics in MoS2 anode for superior sodium storage - Guilong Liu; Wenzhuo Yuan; Zihan Zhao; Jin Li; Naiteng Wu; Donglei Guo; Xiao Liu; Yong Liu; Ang Cao; Xianming Liu (Chemical Engineering Journal, 2024)

Dynamic Mechanical Response and Fracture Characteristics of Multi-flawed Rocks Exposed to Hydrostatic Confinements - Wei You; Feng Dai; Yi Liu; Ang Li (Rock Mechanics and Rock Engineering, 2024)

Effects of Gene Alternative Splicing Events on Resistance to Cryptocaryonosis of Large Yellow Croaker (Larimichthys crocea) - Xin Li; Qiaozhen Ke; Ang Qu; Jiaying Wang; Ji Zhao; Peng Xu; Tao Zhou (Marine Biotechnology, 2024)

The structure of bacteria–fungi bipartite networks along elevational gradients in contrasting climates - Wenqian Zhao; Janne Soininen; Ang Hu; Jinfu Liu; Mingjia Li; Jianjun Wang (Molecular Ecology, 2024)
Climate change is altering species distribution and modifying interactions in microbial communities. Understanding microbial community structure and their interactions is crucial to interpreting ecosystem responses to climate change. Here, we examined the assemblages of stream bacteria and fungi, and the associations between the two groups along elevational gradients in two regions with contrasting precipitation and temperature, that is the Galong and Qilian mountains of the Tibetan Plateau. In the wetter and warmer region, the species richness significantly increased and decreased with elevation for bacteria and fungi, respectively, while were nonsignificant in the drier and colder region. Their bipartite network structure was also different by showing significant increases in connectance and nestedness towards higher elevations only in the wetter and warmer region. In addition, these correlation network structure generally exhibited similar positive association with species richness in the wetter and warmer region and the drier and colder region. In the wetter and warmer region, climatic change along elevation was more important in determining connectance and nestedness, whereas microbial species richness exerted a stronger influence on network structure and robustness in the drier and colder region. These findings indicate substantial forthcoming changes in microbial diversity and network structure in warming climates, especially in wetter and warmer regions on Earth, advancing the understanding of microbial bipartite interactions' response to climate change.

Shellfish CO2 excretion is modulated by seawater carbonate chemistry but largely independent of pCO2 - Minghui Jiao; Jiaqi Li; Meng Zhang; Haonan Zhuang; Ang Li; Longzhen Liu; Suyan Xue; Lulei Liu; Yuze Tang; Yuze Mao (Environmental Science and Pollution Research, 2024)

Association between PM2.5 constituents and cardiometabolic risk factors: Exploring individual and combined effects, and mediating inflammation - Jiaxin Zhao; Yayuan Mei; Ang Li; Quan Zhou; Meiduo Zhao; Jing Xu; Yanbing Li; Kai Li; Ming Yang; Qun Xu (Chemosphere, 2024)

Latitudinal patterns and drivers of plant lignin and microbial necromass accumulation in forest soils: Disentangling microbial and abiotic controls - Jinhong He; Yanxia Nie; Xiangping Tan; Ang Hu; Zhiqi Li; Seping Dai; Qing Ye; Gengxin Zhang; Weijun Shen (Soil Biology and Biochemistry, 2024)

A CNN-SVR model for NO2 profile prediction based on MAX-DOAS observations: The influence of Chinese New Year overlapping the 2020 COVID-19 lockdown on vertical distributions of tropospheric NO2 in Nanjing, China - Xin Tian; Zijie Wang; Pinhua Xie; Jin Xu; Ang Li; Yifeng Pan; Feng Hu; Zhaokun Hu; Mingsheng Chen; Jiangyi Zheng (Journal of Environmental Sciences, 2024)

Aggregation-induced emission nanoparticles facilitating multicolor lateral flow immunoassay for rapid and simultaneous detection of aflatoxin B1 and zearalenone - Yi Zhang; Guoxin Chen; Xirui Chen; Xiaxia Wei; Xuan-ang Shen; Hu Jiang; Xiaoyang Li; Yonghua Xiong; Xiaolin Huang (Food Chemistry, 2024)

Resourceful application and mechanism of oyster shell-microalgae synergistic system：Sustainable treatment of harsh low carbon nitrogen ratio actual wastewater - Yanni Geng; Liming Yang; Chun-Ang Lian; Spyros G. Pavlostathis; Zhiguang Qiu; Zhensheng Xiong; Yuanqi Liu; Bing Li; Jincheng Hu; Wenbo Fan; Xubiao Luo; Ke Yu (Environmental Research, 2024)

Assessment of benthic ecological status and heavy metal contamination in an estuarine intertidal mudflat in the Northern Bohai Sea - Ang Li; Jiaqi Li; Fang Liu; Ling Zhu; Lulei Liu; Suyan Xue; Meng Zhang; Yuze Tang; Yuze Mao (Marine Pollution Bulletin, 2024)

The adaptability, distribution, ecological function and restoration application of biological soil crusts on metal tailings: A critical review - Kejun Liao; Chaoqi Chen; Wenyan Ye; Jing Zhu; Yan Li; Sijia She; Panpan Wang; Yue Tao; Ang Lv; Xinyue Wang; Lanzhou Chen (Science of The Total Environment, 2024)

Non-destructive prediction of ready-to-eat kiwifruit firmness based on Fourier transform near-infrared spectroscopy - Gang Ding; Ke Jin; Xiaoya Chen; Ang Li; Zhiqiang Guo; Yunliu Zeng (Postharvest Biology and Technology, 2024)

New formula of vegetation roughness height and Darcy–Weisbach friction factor in channel flow - Da-Qian Feng; Jing-Jing Fan; Wei-Jie Wang; Cheng-Xing Xia; Ang Li (Journal of Hydrology, 2024)

Elucidating the unexpected importance of intermediate-volatility organic compounds (IVOCs) from refueling procedure - Xinping Yang; Kai Song; Song Guo; Yunjing Wang; Junfang Wang; Di Peng; Yi Wen; Ang Li; Baoming Fan; Sihua Lu; Yan Ding (Journal of Hazardous Materials, 2024)

O3 sensitivity and vertical distribution of summertime HCHO, NO2, and SO2 in Shihezi, China - Hairong Zhang; Ang Li; Shuai Wang; Min Qin; Zhaokun Hu; Jiangman Xu (Atmospheric Pollution Research, 2024)

A neural m6A pathway regulates behavioral aggregation in migratory locusts - Xianliang Huang; Qing Li; Yanan Xu; Ang Li; Shanzheng Wang; Yusheng Chen; Chunrui Zhang; Xia Zhang; Hailin Wang; Cong Lv; Baofa Sun; Shaoqin Li; et al. (Science China Life Sciences, 2024)

Tuning quantum dots emission on DNA tetrahedron/silica nanosphere/graphene oxide nanointerface for ratiometric fluorescence assay of Pb2+ in multiplex samples - Manting Li; Haikun Luo; Zhao Wang; Qian Mo; Shanshan Zhong; Yu-ang Mao; Shuting Li; Xinchun Li (Analytica Chimica Acta, 2024)

Path analysis of body weight and shell morphological traits in two Pacific abalone (Haliotis discus hannai) strains - Ang Li; Jiaqi Li; Lulei Liu; Suyan Xue; Ling Zhu; Yuze Mao (Aquaculture International, 2024)

Leaching behaviors of dissolved organic matter from face masks revealed by fluorescence EEM combined with FRI and PARAFAC - Zhong Jin; Weibo Zhang; Xihuan Wang; Ang Liu; Zhongyu Li; Yingchen Bai; Fengchang Wu (Water Research, 2024)

Quantitative prediction of surrounding rock deformation via an energy-based damage model combining with microseismic monitoring - Dingran Song; Yi Liu; Feng Dai; Ruochen Jiang; Ang Li (Tunnelling and Underground Space Technology, 2024)

Evaluating the multi-variable influence on O3, NO2, and HCHO using BRTs and RF model - Junaid Khayyam; Pinhua Xie; Jin Xu; Xin Tian; Zhaokun Hu; Ang Li (Science of The Total Environment, 2024)

Lateral migration of methane at a cold seep: Evidence from U–Th dating of methane-derived authigenic carbonate in the Middle Okinawa Trough - Ang Li; Nengyou Wu; Zhifeng Wan; Qing Li; Zhilei Sun; Feng Cai; Dong Feng (Marine and Petroleum Geology, 2024)

Can xenobiotics support the growth of Mn(II)-oxidizing bacteria (MnOB)? A case of phenol-utilizing bacteria Pseudomonas sp. AN-1 - Aonan Qiao; Haixia Pan; Jiaxi Zang; Yiwen Zhang; Xianliang Yi; Yang Liu; Jingjing Zhan; Xiaojing Yang; Xu Zhao; Ang Li; Hao Zhou (Journal of Hazardous Materials, 2024)

Angiotoxic effects of chlorinated polyfluorinated ether sulfonate, a novel perfluorooctane sulfonate substitute, in vivo and in vitro - Zhenzhen Tan; Junli Lv; Haoran Li; Ziwen An; Longfei Li; Yijia Ke; Yi Liu; Xuehui Liu; Lei Wang; Ang Li; Huicai Guo (Journal of Hazardous Materials, 2024)

Revolutionary MOF-enhanced anion exchange membrane for precise monovalent anion separation through structural optimization and doping - Junhua Li; Zhipeng Xu; Junbin Liao; Edison Huixiang Ang; Xuanhua Chen; Junjie Mu; Jiangnan Shen (Desalination, 2024)

Illegal synthetic dyes in spices: a Singapore case study - Zan Xin Chin; Sew Lay Chua; Yi Li Ang; Sheena Wee; Ken Kah Meng Lee; Yuansheng Wu; Joanne Sheot Harn Chan (Food Additives & Contaminants Part B-Surveillance, 2024)

Generation estimation and critical metals quantity assessment of retired mobile phones in Japan - Ang Li; Bo Li; Ge Yang; Kronnaphat Khumvongsa; Jingjin Pan; Xiaolong Song; Xuyang Lei; Suxia Hou; Dong Yang; Bin Lu (Journal of Cleaner Production, 2024)

Nitrogen deposition mediates more stochastic processes in structuring plant community than soil microbial community in the Eurasian steppe - Wei Yang; Shuhan Zhang; Ang Li; Junjie Yang; Shuang Pang; Zonghao Hu; Zhiping Wang; Xingguo Han; Ximei Zhang (Science China Life Sciences, 2024)

Spawning, larval morphological ontogeny and first feeding of yellow-striped cardinalfish Ostorhinchus cyanosoma (Bleeker, 1853) - Ang Lu; Xiang-Yu Li; Yi-Yang Lin; Yen-Ju Pan (Aquaculture, 2024)

Reduced toxic effects of nano‑copper sulfate in comparison of bulk CuSO4 on biochemical parameters in the Rohu (Labeo rohita) - Azka Anwar; Fahim Ullah Khan; Waqar Younas; Muhib Zaman; Muhammad Noorullah; Li'ang Li; Amina Zuberi; Youji Wang (Toxicology in Vitro, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Biochar and microorganism assisted phytoremediation of severely molybdenum-contaminated soil: Efficacy, mechanisms and the impact of low temperatures - Chunyan Li; Jie Xing; Qian Xu; Di Cui; Yuqing Liu; Changlong Pang; Ang Li (Journal of Cleaner Production, 2024)

Role of inflammatory lipid and fatty acid metabolic abnormalities induced by plastic additives exposure in childhood asthma - Zhiyu Chen; Fang Li; Lei Fu; Yu Xia; Ying Luo; Ang Guo; Xiaona Zhu; Huifang Zhong; Qian Luo (Journal of Environmental Sciences, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

First record of abnormal body coloration in a rockfish Sebastes koreanus (Scorpaenoidei: Sebastidae) from coastal water of China based on morphological characteristics and DNA barcoding - Ang Li; Huan Wang; Changting An; Shufang Liu (Journal of Oceanology and Limnology, 2024)

Wollastonite powder application increases rice yield and CO2 sequestration in a paddy field in Northeast China - Fangna Wang; Feifei Zhu; Deze Liu; Yuying Qu; Dong Liu; Jin Xie; Ang Wang; Ronghua Kang; Zhi Quan; Yinghua Li; Xin Chen; Guochen Li; et al. (Plant and Soil, 2024)

Porous carboxymethyl cellulose nanocrystalline imprinted composite aerogels for selective adsorption of gadolinium - Tongtong Xu; Ang Li; Xudong Zheng; Biao Ji; Jinfeng Mei; Man Zhou; Zhongyu Li (Chemosphere, 2024)

Effects of elevated temperature and different crystal structures of TiO2 nanoparticles on the gut microbiota of mussel Mytilus coruscus - Zhuoqing Li; Li’ang Li; Inna Sokolova; Yueyong Shang; Wei Huang; Waiho Khor; James K.H. Fang; Youji Wang; Menghong Hu (Marine Pollution Bulletin, 2024)

Transformation mechanisms of ammonium and nitrate in subsurface wastewater infiltration system: Implication for reducing greenhouse gas emissions - Xulun Zhou; Haibo Li; Ang Wang; Geshere Abdisa Gurmesa; Xueyan Wang; Xi Chen; Chenxi Zhang; Yunting Fang (Water Research, 2024)

An AI-powered approach to improving tunnel blast performance considering geological conditions - Yaosheng Liu; Ang Li; Feng Dai; Ruochen Jiang; Yi Liu; Rui Chen (Tunnelling and Underground Space Technology, 2024)

Physiological and histopathological effects of polystyrene nanoparticles on the filter-feeding fish Hypophthalmichthys molitrix - Muhib Zaman; Fahim Ullah Khan; Waqar Younas; Muhammad Noorullah; Imdad Ullah; Li’ang Li; Amina Zuberi; Youji Wang (Science of The Total Environment, 2024)

Early Paleozoic tectonic affinity of the Lesser Xing'an–Zhangguangcai Range, NE China: A continental arc along the western margin of the Jiamusi Block - Qingbin Guan; Boran Liu; Zhaoxu Chen; Yongjiang Liu; Sanzhong Li; Qi'ang Fang; Yujia Du (Lithos, 2024)

Increasing mine waste will induce land cover change that results in ecological degradation and human displacement - John R. Owen; Deanna Kemp; Alex M. Lechner; Michelle Ang Li Ern; Éléonore Lèbre; Gavin M. Mudd; Mark G. Macklin; Muhamad Risqi U. Saputra; Tahjudil Witra; Anthony Bebbington (Journal of Environmental Management, 2024)

Mussel-inspired modification of 2D MoS2 to construct a hybrid nanocomposite membrane with enhanced pervaporation dehydration of isopropanol - Marwin R. Gallardo; Jyun-Xiang Ciou; Chen-Hsiu Wang; Micah Belle Marie Yap Ang; Jeremiah C. Millare; Chi-Lan Li; Hui-An Tsai; Shu-Hsien Huang; Kueir-Rarn Lee (Journal of Environmental Chemical Engineering, 2024)

Influence of methane seep activities and sea-level changes on elemental and isotopic compositions and abundance of carbonates in sediments of the Okinawa Trough since the last glacial period - Qing Li; Hongbin Wang; Feng Cai; Di Luo; Fanxing Kong; Ang Li; Xiting Liu (Journal of Asian Earth Sciences, 2024)

Eco-infused interfacial enhancement of the anti-biofouling activity in anion exchange membranes for electrodialysis desalination - Yuyang Yao; Yueyue Lu; Yuan Li; Yanjing Ma; Edison Huixiang Ang; Jingwen Xu; Heda Ding; Yuna Shi; Yitao Chen; Junbin Liao; Zhenlu Shen; Jiangnan Shen (Chemical Engineering Journal, 2024)

Application of solid electrolytes in electrochemical reduction of CO2 or O2 - Jiayue Li; Zhuowen Wang; Sibei Liu; Zhonglin Chen; Jixian Yang; Zhiqiang Chen; Ang Li; Qinxue Wen; Li Wang; Shan Qiu; Chongwei Cui; Huiyuan Deng; et al. (Chemical Engineering Journal, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Integrated analysis of the transport process and source attribution of an extreme ozone pollution event in Hefei at different vertical heights: A case of study - Feng Hu; Pinhua Xie; Xin Tian; Jin Xu; Ang Li; Aurelia Lupaşcu; Tim Butler; Zhaokun Hu; YinSheng Lv; ZhiDong Zhang; Jiangyi Zheng (Science of The Total Environment, 2024)

Functionally separated electronic band engineering via multi-element doping plus high-density defects advances board-temperature-range thermoelectric performance in GeTe - Jianglong Zhu; Xiaobo Tan; Dong Pan; Yanni Luo; Ruiheng Li; Xuri Rao; Ruihuan Cheng; Chengliang Xia; Yue Chen; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Spinnable hydrogel marbles: A dynamic miniature molecule concentrator for efficient water decontamination and colorimetric detection - Veronica Pereira; Zhi Zhong Ang; Carice Chong; Haitao Li; Hiang Kwee Lee (Chemical Engineering Journal, 2024)

On-demand detachable adhesive hydrogel based on dual dynamic covalent cross-linked with NIR/pH dual-responsive properties for diabetic wound healing - Kaize Su; Duanyu Deng; Xiaoxian Wu; Yumu Song; Ying Sun; Xu Wang; Zhen Zhang; Jinxuan Li; Zhenping Yan; Xiangcun Shang; Chen Li; Kun Zhang; et al. (Chemical Engineering Journal, 2024)

Uncertainty Quantification in Tomographic Inversion of Near-Surface Seismic Refraction Data - Ang Li; Dario Grana; Andrew D. Parsekian; Brad Carr (Mathematical Geosciences, 2024)

Hirsutinolide-type sesquiterpenoids with anti-prostate cancer activity from Cyanthillium cinereum - Song Ang; Chun Liu; Peng Hong; Lei Yang; Gui'e Hu; Xi Zheng; Jingwei Jin; Rihui Wu; Wing-Leung Wong; Kun Zhang; Lishe Gan; Dongli Li (Phytochemistry, 2023)

Identification and characterization of a novel Iflavirus in a stored-product psocid, Liposcelis bostrychophila (Psocodea: Liposcelididae) - Peng-Yu Guo; Dan-Dan Wei; Hua-Yue Feng; Xin-Ping Tang; Yu-Ang Chen; Yi Li; Jin-Jun Wang (Journal of Stored Products Research, 2023)

The cryptic step in the biogeochemical tellurium (Te) cycle: Indirect elementary Te oxidation mediated by manganese-oxidizing bacteria Bacillus sp. FF-1 - Yuqing Liu; Huiqing Ma; Ang Li; Haixia Pan; Xianliang Yi; Yang Liu; Jingjing Zhan; Hao Zhou (Environmental Research, 2023)

Target-oriented functionalization: Turning carbon nitride into a round-the-clock antimicrobial photocatalyst in water disinfection - Fengming Hou; Wei Wei; Yihang Li; Zhipeng Guo; Xiaoke Zhang; Jin Li; Ang Wei (Chemical Engineering Journal, 2023)

Effects of Environmental Heavy Metal Interactions on Renal Impairment: Epidemiological Evidence from Rural Northeastern China - Guohuan Yin; Xiaoyu Ge; Meiduo Zhao; Jing Xu; Ang Li; Yayuan Mei; Jingtao Wu; Xiaolin Liu; Lanping Wei; Qun Xu (Exposure and Health, 2023)

Differential effects of PM2.5 and its carbon components on blood pressure in hypertensive and non-hypertensive populations: a panel study in Beijing - Xue Wang; Ang Li; Meiduo Zhao; Jing Xu; Yayuan Mei; Qun Xu (Environmental Science and Pollution Research, 2023)

Performance of fish sludge solubilization and phototrophic bioconversion by purple phototrophic bacteria for nutrient recovery in aquaponic system - Tian Xia; Ang Chen; Yongxia Zi; Yuan Zhang; Qianzhi Xu; Yueshu Gao; Chunjie Li (Waste Management, 2023)

McPrA - A new gas profile inversion algorithm for MAX-DOAS and apply to 50 m vertical resolution - Jiangyi Zheng; Pinhua Xie; Xin Tian; Jin Xu; Ang Li; Bo Ren; Feng Hu; Zhaokun Hu; Yinsheng Lv; Zhidong Zhang; Wenqing Liu (Science of The Total Environment, 2023)

Particulate organic emissions from incense-burning smoke: Chemical compositions and emission characteristics - Kai Song; Rongzhi Tang; Ang Li; Zichao Wan; Yuan Zhang; Yuanzheng Gong; Daqi Lv; Sihua Lu; Yu Tan; Shuyuan Yan; Shichao Yan; Jingshun Zhang; et al. (Science of The Total Environment, 2023)

The effect of total alkalinity on growth performance and calcification in juvenile Pacific abalone Haliotis discus hannai - Meng Zhang; Jiaqi Li; Minghui Jiao; Yuze Tang; Ang Li; Lulei Liu; Longzhen Liu; Suyan Xue; Yuze Mao (Marine Environmental Research, 2023)

Comprehensive study on particle size distribution, MAH and PAH profiles during alkylbenzene pyrolysis - Pengcheng Zhao; Tie Li; Ang Li; Yongzhi Ma; Mingming Fang; Xinling Li (Fuel, 2023)

Fractional model for simulating Long-Term fracture conductivity decay of shale gas and its influences on the well production - Yu Peng; Ang Luo; Yongming Li; Yijia Wu; Wenjun Xu; Kamy Sepehrnoori (Fuel, 2023)

Reduced nitrogen fertilization from pre-flowering to pre-veraison alters phenolic profiles of Vitis vinifera L. Cv. Cabernet Gernischt wine of Yantai, China - Jianqiang Song; Ang Zhang; Fei Gao; Mingqing Li; Xianhua Zhao; Jie Zhang; Genjie Wang; Yuping Hou; Shiwei Cheng; Huige Qu; Shili Ruan; Jiming Li (Food Research International, 2023)

Multi-omics analyses reveal relationships among polyphenol-rich oolong tea consumption, gut microbiota, and metabolic profile: A pilot study - Ang Li; Ruixin Kou; Haiwei Liu; Mengshan Chen; Jin Wang; Qisijing Liu; Xiaolong Xing; Bowei Zhang; Lu Dong; Shuo Wang (Food Chemistry, 2023)

Advances and promotion strategies of membrane-based methods for extracting lithium from brine - Yu-ning Zhang; De-hao Yu; Chen-yu Jia; Li-yue Sun; Ang Tong; Yao Wang; Yan-xin Wang; Lin-jun Huang; Jian-guo Tang (Desalination, 2023)

Human settlements in the Ordos Plateau since the Neolithic Age - Penghui Wen; Nai’ang Wang; Mingjuan Li; Hongyi Cheng; Zhenmin Niu (Journal of Geographical Sciences, 2023)

Generation estimation and metals recycling potentials evaluation of retired mobile phones in Korea - Ang Li; Bo Li; Huibin Wang; Xia Liu; Yanan Guo; Bin Lu (Environmental Science and Pollution Research, 2023)

Per- and polyfluoroalkyl substances and the associated thyroid cancer risk: A case-control study in China - Haoran Li; Ming Yang; Jing Yang; Samuel Seery; Chaoying Ma; Yi Liu; Xiaoguang Zhang; Ang Li; Huicai Guo (Chemosphere, 2023)

Prospects and perspectives on advanced materials for sodium-ion batteries - Zhen-Yi Gu; Xiao-Tong Wang; Yong-Li Heng; Kai-Yang Zhang; Hao-Jie Liang; Jia-Lin Yang; Edison Huixiang Ang; Peng-Fei Wang; Ya You; Fei Du; Xing-Long Wu (Science Bulletin, 2023)

Thyroid disrupting effects of multiple metals exposure: Comprehensive investigation from the thyroid parenchyma to hormonal function in a prospective cohort study - Ang Li; Quan Zhou; Yayuan Mei; Jiaxin Zhao; Meiduo Zhao; Jing Xu; Xiaoyu Ge; Yanbing Li; Kai Li; Ming Yang; Qun Xu (Journal of Hazardous Materials, 2023)

Observation on the aerosol and ozone precursors in suburban areas of Shenzhen and analysis of potential source based on MAX-DOAS - Hairong Zhang; Ang Li; Zhaokun Hu; Hongmei Ren; Hongyan Zhong; Jianfeng Guo; Long Yun; Mingdi Zhang (Journal of Environmental Sciences, 2023)

Insight of soot nanostructure and oxidation behavior in ammonia / ethylene coaxial diffusion flame - Luoxi Wang; Fei Ren; Xiaogang Cheng; Zhan Gao; Ang Li; Lei Zhu; Zhen Huang (Fuel, 2023)

Performance enhancement of proton exchange membrane fuel cells with bio-inspired gear-shaped flow channels - Yuzhi Ke; Baotong Zhang; Wei Yuan; Yafeng Bai; Yonghao Zhao; Zi'ang Liu; Zhenhe Lin; Xinze Li; Yangang Wang; Yong Tang (Chemical Engineering Journal, 2023)

Carbon-based hierarchical porous structure accelerates heterogeneous nucleation of PEG molecules for solar/electro-driven thermal energy storage - Ruze Liu; Ang Li; Jinyan Liu; Wengeng Liu; Hao Zheng; Qingyang Du; Xiao Chen; Cheng Dong (Chemical Engineering Journal, 2023)

Ectopic Expression of Pineapple Actin-Related Protein 6 (AcARP6) Regulates Flowering and Stress Responses in Arabidopsis - Bello Hassan Jakada; Beenish Fakher; Li-Ang Yao; Xiaomei Wang; Mohammad Aslam; Yuan Qin (Journal of Plant Growth Regulation, 2023)

Sensitivity and control efficacy of a novel complex III inhibitor pyribencarb against Sclerotinia sclerotiorum - Ang Li; Hongjie Liang; Xinyi Cui; Weixu Yang; Xin Zhou; Pengwen Zeng; Dingzhi Pang; Shenjv Xia; Hongying Shan; Ning Li; Jinli Li (Journal of Plant Diseases and Protection, 2023)

A glance of coupled water and wastewater treatment systems based on microbial fuel cells - Yulong Huang; Yaqian Zhao; Cheng Tang; Asheesh Kumar Yadav; Rouzbeh Abbassi; Peiying Kang; Yamei Cai; Ang Liu; Anran Yang; Min Li (Science of The Total Environment, 2023)

The DYW domain of RARE1 plays an indispensable role in regulating accD-C794 RNA editing in Arabidopsis thaliana - Dan Liu; Zi-Ang Li; Yi Li; David P. Molloy; Chao Huang (Plant Science, 2023)

A new insight into the CaO-induced inhibition pathways on PCDD/F formation: Metal passivation, dechlorination and hydroxide substitution - Xiaoxiao Wang; Jiabao Lv; Yuxuan Ying; Yunfeng Ma; Angjian Wu; Xiaoqing Lin; Ang Cao; Xiaodong Li; Jianhua Yan (Science of The Total Environment, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Fire resistance evaluation of laminated bamboo lumber column under eccentric compression - Zhaoyan Cui; Ming Xu; Ang Li; Liuhui Tu; Jia Zhu; Yurong Shen (Engineering Structures, 2023)

Continuous degradation of plasticizer bisphenol A by catalytic Cu(Fe Al )O @sediment ceramic membranes combined with peroxymonosulfate activation - Zhe Xu; Guangfu Luo; Yi'ang Fan; Yunxue Xia; Jiangpeng Li; Jianshuai Zhang; Kaimin Shih; Yuanyuan Tang (Chemical Engineering Journal, 2023)

Correction to: Cucumis sativus PHLOEM PROTEIN 2-A1 like gene positively regulates salt stress tolerance in cucumber seedlings - Yuyang Si; Huaifu Fan; Hongjie Lu; Yapeng Li; Yuting Guo; Chen Liu; Li’ang Chai; Changxia Du (Plant Molecular Biology, 2023)

Failure mechanism of underwater shield tunnel: An experimental and theoretical study - Kun Liang; Kun Feng; Li Zhang; Chuan He; Ang Su; Wenqi Guo (Tunnelling and Underground Space Technology, 2023)

Dietary exposure to nTiO2 reduces byssus performance of mussels under ocean warming - Saishuai Li; Hui Chen; Chunhua Liu; Inna M. Sokolova; Yuchuan Chen; Fujing Deng; Zhe Xie; Li'ang Li; Wei Liu; James Kar-Hei Fang; Daohui Lin; Menghong Hu; et al. (Science of The Total Environment, 2023)

Combined toxic effects of nanoplastics and norfloxacin on mussel: Leveraging biochemical parameters and gut microbiota - Ran Xu; Li'ang Li; Jiahui Zheng; Chenglong Ji; Huifeng Wu; Xiang Chen; Yuchuan Chen; Menghong Hu; Elvis Genbo Xu; Youji Wang (Science of The Total Environment, 2023)

Quantitative analysis of the minimum days of dietary survey to estimate dietary pesticide exposure: Implications for dietary pesticide sampling strategy - Ang Li; Ming Yang; Yayuan Mei; Quan Zhou; Jiaxin Zhao; Yanbing Li; Kai Li; Meiduo Zhao; Jing Xu; Qun Xu (Environmental Pollution, 2023)

Nitrogen-doped carbon confined Cu-Ag bimetals for efficient electroreduction of CO2 to high-order products - Xinyao Zou; Ang Li; Chao Ma; Zhan Gao; Baowen Zhou; Lei Zhu; Zhen Huang (Chemical Engineering Journal, 2023)

The thermodynamics of enhanced dope stability of cellulose solution in NaOH solution by urea - Yu Chen; Yoshiharu Nishiyama; Ang Lu; Yan Fang; Ziqiang Shao; Tao Hu; Dongdong Ye; Haisong Qi; Xiaodong Li; Jakob Wohlert; Pan Chen (Carbohydrate Polymers, 2023)

Dynamic Responses and Failure Behaviors of Saturated Rocks Subjected to Repetitive Compression–Shear Impacting - Hongbo Du; Feng Dai; Ang Li; Ruochen Jiang (Rock Mechanics and Rock Engineering, 2023)

Using DORIS data for validating real-time GNSS ionosphere maps - Ang Liu; Ningbo Wang; Denise Dettmering; Zishen Li; Michael Schmidt; Liang Wang; Hong Yuan (Advances in Space Research, 2023)

DUSP2 Deletion Inhibits Macrophage Migration by Inhibiting ERK Activation in Zebrafish - Yu-Jiao Li; Xin-Liang Wang; Ling-Yu Shi; Zong-Yi Wang; Zi-Ang Zhao; Shu-Chao Ge; Bing Hu (Fishes, 2023)
Dual-specificity phosphatase 2 (DUSP2) regulates the activation of members of the mitogen-activated protein kinase (MAPK) family, which is involved in a variety of cellular processes including cell proliferation, differentiation, apoptosis, and migration. DUSP2 also regulates the expression of inflammatory mediators in macrophages; however, it remains unknown whether DUSP2 participates in macrophage migration. Here, using the tail fin injury model in zebrafish larvae, we found that the deletion of DUSP2 inhibited the expression of pro-inflammatory cytokines and macrophage chemokines. Moreover, live imaging results showed that the migration of macrophages to the injury site was inhibited after DUSP2 deletion. This inhibitory effect was mediated through the reduced activation of extracellular regulated protein kinases (ERK) in DUSP2 knockout zebrafish.

Valorization of thermally hydrolyzed sludge with clay for sintering of ceramic tiles - Lei Wen; Lin Lin; Yi-ang Fan; Yang Luo; Sheng-shou Ma; Ying Zhou; Chao Yang; Kaimin Shih; Xiao-yan Li (Science of The Total Environment, 2023)

Evaluation and measurement of tropospheric glyoxal retrieved from MAX-DOAS in Shenzhen, China - Hairong Zhang; Ang Li; Zhaokun Hu; Jianfeng Guo; Long Yun; Mingdi Zhang; Hongmei Ren; Hongyan Zhong; Jiangman Xu (Science of The Total Environment, 2023)

Intracellular electron competition in response to the oxygen pressure of the aerobic denitrification process in an O2-based membrane biofilm reactor (MBfR) for nitrate removal - Liang Feng; Fei-yun Sun; Jixian Yang; Di Cui; Zuo-hua Li; Shanshan Pi; He-Ping Zhao; Ang Li (Science of The Total Environment, 2023)

In situ reductive dehalogenation of groundwater driven by innovative organic carbon source materials: Insights into the organohalide-respiratory electron transport chain - Yang Yu; Yueyan Zhang; Yuqing Liu; Mengran Lv; Zeyi Wang; Li-lian Wen; Ang Li (Journal of Hazardous Materials, 2023)

Piezoelectric energy harvesting and dissipating behaviors of polymer-based piezoelectric composites for nanogenerators and dampers - Wenzheng Chen; Qitan Zheng; Yi Ang Lv; Yujie Chen; Qunfu Fan; Xunhuang Zhou; Hua Li; Qili Yu; Hezhou Liu (Chemical Engineering Journal, 2023)

Atomic defects engineering on Fe-N4 sites for boosting oxygen reduction by in-situ ZnO thermal etching strategy - Shengjie Wei; Lei Li; Ang Li; Lei Zhang; Haibo Hu; Dawei Pang; Qinghua Zhang; Hai Xiao; Wenxing Chen (Chemical Engineering Journal, 2023)

X-ray diffraction and the symmetry of ultrathin crystalline materials between two-dimensional and three-dimensional crystals - Hengrui Ma; Qiaorong Jiang; Zi-Ang Nan; Gen Li; Yanyan Jia; Ruoxin Ning; Jia-Bao Ji; Zhenming Cao; Linzhe Lü; Huiqi Li; Sheng Dai; Haixin Lin; et al. (Science Bulletin, 2023)

A review of additives use in straw composting - Mingyue Piao; Ang Li; Huishi Du; Yuwei Sun; Hongxue Du; Honghui Teng (Environmental Science and Pollution Research, 2023)

Associations of metals and metals mixture with lipid profiles: A repeated-measures study of older adults in Beijing - Ang Li; Yanbing Li; Yayuan Mei; Jiaxin Zhao; Quan Zhou; Kai Li; Meiduo Zhao; Jing Xu; Xiaoyu Ge; Qun Xu (Chemosphere, 2023)

Differential physiological response of marine and freshwater microalgae to polystyrene microplastics - Hengtao Xu; Li’ang Li; Youji Wang; Kecheng Qiu; Siyang Chen; Jiangning Zeng; Ruijuan Liu; Qikun Yang; Wei Huang (Journal of Hazardous Materials, 2023)

Integrated mRNA and miRNA expression analyses for Cryptocaryon irritans resistance in large yellow croaker (Larimichthys crocea) - Ang Qu; Yulin Bai; Jiaying Wang; Ji Zhao; Junjia Zeng; Yue Liu; Xintong Chen; Qiaozhen Ke; Pengxin Jiang; Xinyi Zhang; Xin Li; Peng Xu; et al. (Fish & Shellfish Immunology, 2023)

Cucumis sativus PHLOEM PROTEIN 2-A1 like gene positively regulates salt stress tolerance in cucumber seedlings - Yuyang Si; Huaifu Fan; Hongjie Lu; Yapeng Li; Yuting Guo; Chen Liu; Li’ang Chai; Changxia Du (Plant Molecular Biology, 2023)

Isolation and identification of the molybdenum-resistant strain Raoultella ornithinolytica A1 and its effect on MoO42− in the environment - Jie Xing; Chunyan Li; Wanting Li; Xuemei Zhang; Zhaoquan Li; Ang Li (Biodegradation, 2023)

scRNA-seq analysis reveals toxicity mechanisms in shrimp hemocytes subjected to nitrite stress - QingJian Liang; BeiBei Dong; Ang Li; LiTing Wu; Yu Zhang; Tao Han; Xing Liu (Chemosphere, 2023)

Characteristics and source analysis of polycyclic aromatic hydrocarbons in organisms and manure near Ardley Island, Antarctica - Bin Han; Gui Wang; Ang Liu; Yunchao Zheng; Li Zheng; Runtian Ding (Marine Pollution Bulletin, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

Variability, Clearance, and Concentration of Multiple Metals and Risk of Kidney Function Abnormality: A New Integrative Metal Exposure Assessment Approach - Ang Li; Jiaxin Zhao; Yayuan Mei; Quan Zhou; Meiduo Zhao; Jing Xu; Xiaoyu Ge; Qun Xu (Exposure and Health, 2023)

Enhanced foliar 15 N enrichment with increasing nitrogen addition rates: Role of plant species and nitrogen compounds - Yinliu Wang; Guoxiang Niu; Ruzhen Wang; Kathrin Rousk; Ang Li; Muqier Hasi; Changhui Wang; Jianguo Xue; Guojiao Yang; Xiaotao Lü; Yong Jiang; Xingguo Han; et al. (Global Change Biology, 2023)
Determining the abundance of N isotope (δ 15 N) in natural environments is a simple but powerful method for providing integrated information on the N cycling dynamics and status in an ecosystem under exogenous N inputs. However, whether the input of different N compounds could differently impact plant growth and their 15 N signatures remains unclear. Here, the response of 15 N signatures and growth of three dominant plants ( Leymus chinensis , Carex duriuscula , and Thermopsis lanceolata ) to the addition of three N compounds (NH 4 HCO 3 , urea, and NH 4 NO 3 ) at multiple N addition rates were assessed in a meadow steppe in Inner Mongolia. The three plants showed different initial foliar δ 15 N values because of differences in their N acquisition strategies. Particularly, T. lanceolata (N 2 ‐fixing species) showed significantly lower 15 N signatures than L. chinensis (associated with arbuscular mycorrhizal fungi [AMF]) and C. duriuscula (associated with AMF). Moreover, the foliar δ 15 N of all three species increased with increasing N addition rates, with a sharp increase above an N addition rate of ~10 g N m −2 year −1 . Foliar δ 15 N values were significantly higher when NH 4 HCO 3 and urea were added than when NH 4 NO 3 was added, suggesting that adding weakly acidifying N compounds could result in a more open N cycle. Overall, our results imply that assessing the N transformation processes in the context of increasing global N deposition necessitates the consideration of N deposition rates, forms of the deposited N compounds, and N utilization strategies of the co‐existing plant species in the ecosystem.

Comparison of alive and dead benthic foraminiferal fauna off the Changjiang Estuary: Understanding water-mass properties and taphonomic processes - Feng Jiang; Daidu Fan; Quanhong Zhao; Yijing Wu; Fahui Ren; Yan Liu; Ang Li (Frontiers in Marine Science, 2023)
Benthic foraminifera (BF) are utilized in palaeo-environmental reconstruction based on our understanding of how living individuals respond to environmental variations. However, there is still a lack of empirical insight into how non-environmental factors, such as taphonomic processes, influence the preservations of fossil BF in strata. In this study, we compare the spatial distribution and composition of alive and dead BF fauna in surface sediments to elucidate how well fossil foraminiferal fauna mirror quasi-contemporary alive BF groups indicative of different water masses off a mega-river (Changjiang) estuary, which is characterized by intense and complex river-sea interactions. On-site measurements of bottom water salinity, temperature, and dissolved oxygen were conducted in the summer to determine water mass properties. A same-site comparison of alive (Rose Bengal stained) and dead foraminiferal fauna in surface sediment samples over 73 stations was then carried out. Q-mode Hierarchical clustering analysis was used to differentiate foraminiferal assemblages based on the relative abundance of common species. Three distinct regions with different water-mass properties were identified. The distribution pattern of dead foraminiferal fauna is mainly inherited from alive fauna, while the density and diversity of the dead fauna were found to be higher than those of the alive one. Both alive and dead fauna were clustered into four assemblages. A few common alive species (small-agglutinated and thin-calcareous) were rarely found in dead fauna, and a few common dead species (preferring low temperature and indicating allochthonous sources) were rarely present in alive fauna. The alive foraminiferal abundance and diversity were mainly determined by food resources and environmental properties of salinity and temperature. Alive foraminiferal assemblages were separated by different water masses determined by river-sea interactions off the Changjiang Estuary. The “time-averaging” effect was found to be responsible for the higher density and diversity of the dead fauna. Disintegration of agglutinated tests, dissolution of calcareous tests and selective transportation were observed to contribute to the different species compositions between the alive and dead fauna. Nevertheless, indicative species-environment relations in alive and taphocoenose fauna were found to be almost homologous among most common species. This suggests that distinct benthic foraminiferal assemblages can be used to effectively differentiate between different water masses in the study coastal seas.

Submerged macrophytes mediated remediation of molybdenum-contaminated sediments - Jie Xing; Chunyan Li; Zhaoquan Li; Wanting Li; Ailun Fang; Ang Li (Environmental Science and Pollution Research, 2023)

PFAS-induced lipidomic dysregulations and their associations with developmental toxicity in zebrafish embryos - Zhiyi Yang; Lei Fu; Mengxi Cao; Fang Li; Jingguang Li; Zhiyu Chen; Ang Guo; Huifang Zhong; Wenbo Li; Yong Liang; Qian Luo (Science of The Total Environment, 2023)

Maternal exposure to 4-vinylcyclohexene diepoxide during pregnancy induces subfertility and birth defects of offspring in mice - Wei Song; Ang Li; Qian-Qian Sha; Shao-Yuan Liu; Yong Zhou; Chang-Yin Zhou; Xue Zhang; Xiao-Zhen Li; Jia-Xin Jiang; Fei Li; Chao Li; Heide Schatten; et al. (Science of The Total Environment, 2023)

Palaeoenvironmental evolution of the Badain Jaran Desert hinterland during the Early to Middle Holocene: A multi-proxy reconstruction on Taoerlegetu paleolake, northwest China - Chen’ao Lu; Nai'’ang Wang; Lvlv Zhang; Zhuolun Li; Wenwei Zhao; Meng Li; Xianbao Su; Yixin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Characterization and shifting of microbial community to denitrification for anaerobic sulfamethoxazole biodegradation with different electron acceptors - Xiaoli Su; Feiyun Sun; Jianjun Zhang; Dingyu Xing; Xiaoying Li; Zi Song; Liang Feng; Zhichao Huang; Ang Li (Journal of Cleaner Production, 2023)

Co-variation of crustal thermal condition and thickness of the northeastern margin of Kazakhstan continent during the Late Paleozoic Siberia-Kazakhstan convergence and post-collisional extension - Yan Xu; Bao-Fu Han; Ang Li; Wen Liao (Journal of Asian Earth Sciences, 2023)

Numerical analysis on burning and particle formation of a single ethanol-based droplet in flame spray pyrolysis - Shengfeng Luo; Lun'ang Li; Bo Zhou (Fuel, 2023)

Trace elements and Alzheimer dementia in population-based studies: A bibliometric and meta-analysis - Kai Li; Ang Li; Yayuan Mei; Jiaxin Zhao; Quan Zhou; Yanbing Li; Ming Yang; Qun Xu (Environmental Pollution, 2023)

Zinc Deficiency Induces Inflammation and Apoptosis via Oxidative Stress in the Kidneys of Mice - Yueqi Xu; Ang Li; Xiang Li; Xian Deng; Xue-jiao Gao (Biological Trace Element Research, 2023)

Low-temperature-resistance granulation of activated sludge and the microbial responses to the granular structural stabilization - Chunyan Yuan; Feiyun Sun; Jianjun Zhang; Liang Feng; Honghua Tu; Ang Li (Chemosphere, 2023)

Key emergency response technologies for abrupt air pollution accidents in China - Jun Duan; Shushuai Mao; Pinhua Xie; Jianlei Lang; Ang Li; Jingjing Tong; Min Qin; Jin Xu; Zeya Shen (Journal of Environmental Sciences, 2023)

Fundamental study on oxidation properties at elevated pressure of typical renewable synthetic liquid fuels through low-temperature CO2 electroreduction - Zhenyingnan Zhang; Ang Li; Zheng Ma; Zhen Huang; Lei Zhu (Fuel, 2023)

Association of long-term air pollution exposure with the risk of prediabetes and diabetes: Systematic perspective from inflammatory mechanisms, glucose homeostasis pathway to preventive strategies - Yayuan Mei; Ang Li; Jiaxin Zhao; Quan Zhou; Meiduo Zhao; Jing Xu; Runkui Li; Yanbing Li; Kai Li; Xiaoyu Ge; Chen Guo; Yongjie Wei; et al. (Environmental Research, 2023)

Ionic liquid etched and microwave-assisted delaminated MXene as an excellent electrocatalyst for the hysteretic negative reaction of vanadium redox flow batteries - Minghua Jing; Xi Li; Hao Yu; Xinyu An; Zhuling Liu; Ang Zhang; Xindong Qin; Chao Li; Dawei Fang (Chemical Engineering Journal, 2023)

Advanced layered oxide cathodes for sodium/potassium-ion batteries: Development, challenges and prospects - Zhi-Xiong Huang; Zhen-Yi Gu; Yong-Li Heng; Edison Huixiang Ang; Hong-Bo Geng; Xing-Long Wu (Chemical Engineering Journal, 2023)

Associations and burdens of relative humidity with cause-specific mortality in three Chinese cities - Yayuan Mei; Ang Li; Meiduo Zhao; Jing Xu; Runkui Li; Jiaxin Zhao; Quan Zhou; Xiaoyu Ge; Qun Xu (Environmental Science and Pollution Research, 2023)

A feasibility study on the use of hydrophobic eutectic solvents as pseudo-stationary phases in capillary electrophoresis for chiral separations - Ang Li; Song Xue; Yu Xu; Sihui Ding; Di Wen; Qi Zhang (Analytica Chimica Acta, 2023)

SHAKING: Adjusted spherical harmonics adding KrigING method for near real-time ionospheric modeling with multi-GNSS observations - Ang Liu; Zishen Li; Ningbo Wang; Yan Zhang; Andrzej Krankowski; Hong Yuan (Advances in Space Research, 2023)

Hematodinium perezi naturally infects Asian brush‐clawed crab ( Hemigrapsus takanoi ) - Miao Gong; Guosi Xie; Hailiang Wang; Xinshu Li; Ang Li; Xiaoyuan Wan; Jingxian Huang; Chengyin Shi; Qingli Zhang; Jie Huang (Journal of Fish Diseases, 2023)
The parasitic dinoflagellates of the genus Hematodinium have been considered one of the most important emerging pathogens for a broad range of marine crustaceans around the world. In China, frequent outbreaks of Hematodinium infections have caused serious economic losses for local farmers since 2004. Wild crabs were recently indicated to play a vital role in the transmission and spreading of the Hematodinium disease in polyculture pond systems. Based on PCR amplification and histopathological examination, we demonstrated that H. perezi can naturally infect a wild crab species, Hemigrapsus takanoi , which were collected from the waterways located on the coast of Rizhao or Weifang, Shandong Peninsula, China. According to the sequence similarity analysis and phylogenetic analysis, the Hematodinium isolates were identified as H. perezi and belonged to genotype II. The prevalence of H. perezi ranged from 3.3% to 5.7% in H. takanoi originating from Rizhao ( n = 165 wild crabs) and from 0.9% to 20.0% in that originating from Weifang ( n = 1386 wild crabs), respectively. To our knowledge, H. takanoi is, for the first time, reported as a new host for Hematodinium. Given the wide distribution of H. takanoi on the coasts along the Shandong Peninsula and the relative high prevalence of infection we monitored in our study, we speculate that H. takanoi contributes to the introducing and spreading parasitic Hematodinium between ponds via waterways in a poly‐culturing system. Findings in this study broaden the host range of this parasite and expand the scope of our surveillance for Hematodinium disease in China.

The Combination of Platelet Rich Plasma Gel, Human Umbilical Mesenchymal Stem Cells and Nanohydroxyapatite/polyamide 66 Promotes Angiogenesis and Bone Regeneration in Large Bone Defect - Wei Liu; Yong Huang; Daqian Liu; Teng Zeng; Jingzhe Wang; Ang Li; Dawei Wang; Xiaoyu Wang (Tissue Engineering and Regenerative Medicine, 2022)

Hsa_circ_0006732 regulates colorectal cancer cell proliferation, invasion and EMT by miR-127-5p/RAB3D axis - Tao Yang; Jufeng Sun; Wei Wang; Dongsheng Li; Xianxu Yang; Ang Jia; Yinda Ma; Zhongkai Fan (Molecular and Cellular Biochemistry, 2022)

Correction: Geostatistical Rock Physics Inversion for Predicting the Spatial Distribution of Porosity and Saturation in the Critical Zone - Dario Grana; Andrew D. Parsekian; Brady A. Flinchum; Russell P. Callahan; Natalie Y. Smeltz; Ang Li; Jorden L. Hayes; Brad J. Carr; Kamini Singha; Clifford S. Riebe; W. Steven Holbrook (Mathematical Geosciences, 2022)

Geostatistical Rock Physics Inversion for Predicting the Spatial Distribution of Porosity and Saturation in the Critical Zone - Dario Grana; Andrew D. Parsekian; Brady A. Flinchum; Russell P. Callahan; Natalie Y. Smeltz; Ang Li; Jorden L. Hayes; Brad J. Carr; Kamini Singha; Clifford S. Riebe; W. Steven Holbrook (Mathematical Geosciences, 2022)

Ages and tectonic attributes of Late Palaeozoic stratigraphic units in the Tarbagatay, West Junggar (NW China): revisited - Yan Xu; Ang Li; Wen Liao; Bao-Fu Han (International Geology Review, 2022)

Generation estimation and material flow analysis of retired mobile phones in China - Ang Li; Bo Li; Bin Lu; Dong Yang; Suxia Hou; Xiaolong Song (Environmental Science and Pollution Research, 2022)

From ambiguity to transparency: influence of environmental information disclosure on financial performance in the context of internationalization - Ge Wang; Qi’ang Du; Xiaodong Li; Xiaopeng Deng; Yanliang Niu (Environmental Science and Pollution Research, 2022)

Design Theory and Physical Simulation Test Using a Textile Bag to Control Water Inrush in a Coal Mine Roadway - Ang Li; Yuxuan Yang; Mingcheng Zhu; Wenzhong Zhang; Bingnan Ji; Xuesong Ding (Mine Water and the Environment, 2022)

Microfluidic preparation of a novel phoxim nanoemulsion pesticide against Spodoptera litura - Zong-Nan Li; Yu-Xuan Zhang; Zhi-Ang Zhang; Lian-Han Pan; Ping Li; Yan Xu; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2022)

The Landscape of DNA Methylation Generates Insight Into Epigenetic Regulation of Differences Between Slow-Twitch and Fast-Twitch Muscles in Pseudocaranx dentex - Busu Li; Huan Wang; Ang Li; Changting An; Ling Zhu; Shufang Liu; Zhimeng Zhuang (Frontiers in Marine Science, 2022)
Skeletal muscles of teleost are mainly composed of slow-twitch muscles (SM) and fast-twitch muscles (FM) differed in contractile properties, metabolic capacities, and regeneration rate. The transcriptional regulatory mechanisms that control different muscle types have been elucidated in teleost according to transcriptome between SM and FM. However, the differences between SM and FM were affected not only by genotype but also by complicated epigenetic effects, including DNA methylation, which usually regulates genes in transcription level. To determine the essential role of DNA methylation in the regulation of different muscle types, we analyzed whole-genome methylation profiles of pelagic migratory fish Pseudocaranx dentex with abundant and well-separated SM and integrated DNA methylation profiles with the previously obtained transcriptome data. A total of 4,217 differentially methylated genes (DMGs) were identified, of which 3,582 were located in the gene body and 635 in the promoter. These DMGs mainly participated in muscle metabolite and cell junction. Enriched cell junction pathway reflected different capillary distribution between SM and FM. Through comprehensive analysis of methylome and transcriptome, 84 differentially expressed genes (DEGs) showed significant methylation variation in promoters between SM and FM, indicating that their expression was regulated by DNA methylation. Hypomethylated and highly expressed oxygen storage protein Myoglobin ( myg ) in SM indicated demethylation of myg promoter could upregulate its expression, thus increasing O 2 supplying and meeting oxygen demands of SM. Hypermethylated and lowly expressed tnn (Troponin) and rlc (myosin regulatory light chain) in SM may be associated with low mobility of myosin cross bridges, which lead to slower and less frequent muscle contraction in SM than in FM. In addition, hypomethylated and highly expressed lbx1 (Ladybird homeobox protein homolog 1) and epo (erythropoietin) may be related to increased satellite cell numbers, and Semaphorin/Plexin genes may be related to higher rate of neuromuscular connection reconstruction, which further promote high muscle regeneration efficiency in SM. Our study elucidated the potential DNA methylation mechanisms that regulate physiological characteristics differences between SM and FM, which could facilitate our understanding of skeletal muscle adaptation in pelagic migratory fishes and further enrich the theoretical basis for the study of physiological characteristics and adaptive evolution in teleost fishes.

Recent Progress in Modeling and Control of Bio-Inspired Fish Robots - Boai Sun; Weikun Li; Zhangyuan Wang; Yunpeng Zhu; Qu He; Xinyan Guan; Guangmin Dai; Dehan Yuan; Ang Li; Weicheng Cui; Dixia Fan (Journal of Marine Science and Engineering, 2022)
Compared with traditional underwater vehicles, bio-inspired fish robots have the advantages of high efficiency, high maneuverability, low noise, and minor fluid disturbance. Therefore, they have gained an increasing research interest, which has led to a great deal of remarkable progress theoretically and practically in recent years. In this review, we first highlight our enhanced scientific understanding of bio-inspired propulsion and sensing underwater and then present the research progress and performance characteristics of different bio-inspired robot fish, classified by the propulsion method. Like the natural fish species they imitate, different types of bionic fish have different morphological structures and distinctive hydrodynamic properties. In addition, we select two pioneering directions about soft robotic control and multi-phase robotics. The hybrid dynamic control of soft robotic systems combines the accuracy of model-based control and the efficiency of model-free control, and is considered the proper way to optimize the classical control model with the intersection of multiple machine learning algorithms. Multi-phase robots provide a broader scope of application compared to ordinary bionic robot fish, with the ability of operating in air or on land outside the fluid. By introducing recent progress in related fields, we summarize the advantages and challenges of soft robotic control and multi-phase robotics, guiding the further development of bionic aquatic robots.

Canonical transformation for multivariate mixed model association analyses - Li’ang Yang; Ying Zhang; Yuxin Song; Hengyu Zhang; Runqing Yang (Theoretical and Applied Genetics, 2022)

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Roles of neutrophil reactive oxygen species (ROS) generation in organ function impairment in sepsis - Jiaqi Lu; Jingyuan Liu; Ang Li (Journal of Zhejiang University-SCIENCE B, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effect of confining pressure on peak penetration force of the TBM disc cutter - Wu Li; Peng Yan; Ang Lu; Shuling Huang; Wenbo Lu (Arabian Journal of Geosciences, 2022)

Genome-wide CRISPR activation screen identifies candidate receptors for SARS-CoV-2 entry - Shiyou Zhu; Ying Liu; Zhuo Zhou; Zhiying Zhang; Xia Xiao; Zhiheng Liu; Ang Chen; Xiaojing Dong; Feng Tian; Shihua Chen; Yiyuan Xu; Chunhui Wang; et al. (Science China Life Sciences, 2022)

The association between urine elements and fasting glucose levels in a community-based elderly people in Beijing - Liu Liu; Ang Li; Qun Xu; Qin Wang; Feng Han; Chunyu Xu; Zhe Liu; Dongqun Xu; Donggang Xu (Environmental Science and Pollution Research, 2022)

Biodiversity and degradation potential of oil-degrading bacteria isolated from sediments of hydrothermal and non-hydrothermal areas of the Southwest Mid-Indian Ocean Ridge - Haolei Shi; Jiangfeng Cheng; Wei Gao; Meng Ma; Ang Liu; Tianyi Hu; Bin Han; Li Zheng (Environmental Science and Pollution Research, 2022)

Identification of structural variation and polymorphisms of a sex co-segregating scaffold in spinach - Li’ang Yu; Xiaokai Ma; William Wadlington; Ray Ming (Plant Reproduction, 2022)

Species richness and generalists–specialists mosaicism of symbiodiniacean symbionts in corals from Hong Kong revealed by high-throughput ITS sequencing - Osama S. Saad; Xin Lin; Tsz Yan Ng; Ling Li; Put Ang; Senjie Lin (Coral Reefs, 2022)

Improved Agrobacterium tumefaciens-mediated transformation using antibiotics and acetosyringone selection in cucumber - Changxia Du; Li’ang Chai; Chen Liu; Yuyang Si; Huaifu Fan (Plant Biotechnology Reports, 2022)

Optimizing Microalgae Diet, Temperature, and Salinity for Dwarf Surf Clam, Mulinia lateralis, Spat Culture - Zujing Yang; Hao Wang; Moli Li; Mingxuan Teng; Xuefeng Wang; Ang Zhao; Xiaoting Huang; Jingjie Hu; Zhenmin Bao (Frontiers in Marine Science, 2022)
Dwarf surf clam, Mulinia lateralis , is widely considered as a model species for bivalves. The development of a standard culture system could greatly promote the production of high-quality individuals, yet information on the culture conditions for M. lateralis spat is still limited. This study aims to determine the suitable microalgae diet, temperature, and salinity for M. lateralis spat culture. The typically fed microalgae species, including Chlorella pyrenoidesa (Cp), Platymonas helgolandica (Ph), Dunaliella salina (Ds), Nitzschia closterium (Nc), and Chaetoceros muelleri (Cm), could be taken up by M. lateralis spat, and their filtration rates on Cp, Nc, and Cm were higher than those on Ds and Ph. For the entire spat culture, all diet trials showed similar survival percentages, while the mono-specific diet Cp exhibited the highest growth rate, suggesting that Cp was the optimal microalgae species for M. lateralis spat. Through simultaneously maximizing the growth and survival of spat, the optimal microalgae concentration and stocking density were 5 × 10 4 cells ml –1 and 400–600 individuals m –2 for 30–40-day-old spat as well as 1 × 10 5 cells ml –1 and 400–600 individuals m –2 for 40–50-day-old spat, respectively. In addition, the spat had higher growth rates and survival percentages at the temperature of 20–22°C and salinity of 22–25 ppt. The results of this study provide a basis for further culture of M. lateralis spat, and the optimized conditions will be of great significance for the construction of the standard culture system of M. lateralis .

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

A satellite-based method for modeling ionospheric slant TEC from GNSS observations: algorithm and validation - Wen Li; Zishen Li; Ningbo Wang; Ang Liu; Kai Zhou; Hong Yuan; Andrzej Krankowski (GPS Solutions, 2022)
Total Electron Content (TEC) modeling is critical for Global Navigation Satellite System (GNSS) users to mitigate ionospheric delay errors. The mapping function is usually used for Vertical TEC ionospheric correction models for slant and vertical TEC conversion. But the mapping function cannot characterize TEC variation in different azimuths between the user and satellites. The ionospheric modeling error resulting from the mapping function tends to be bigger in middle and low latitudes. Therefore, a new algorithm for ionospheric Slant TEC (STEC) modeling with Satellite-based Ionospheric Model (SIM) is proposed in this contribution. Validation tests are carried out with GNSS observation data from the Crustal Movement Observation Network of China during different solar activities and in different seasons. The performance of SIM is compared with that of several commonly-used Global Ionospheric Map (GIM) and Regional Ionospheric Map (RIM) products. The results show that the STEC bias and STD of SIM are within 1.0 TECU and about 2.0 TECU, respectively, and SIM can correct over 90% STEC RMS errors, outperforming the GIM and RIM products. Consequently, the SIM algorithm can be a new option for high-accuracy ionospheric delay correction in regional and local GNSS networks.

Research on support method in soft rock tunnel considering the rheological characteristics of rock - Xiao-long Guo; Yong-quan Zhu; Zhong-sheng Tan; Lei Li; Ang Li; Ya-tao Yan (Arabian Journal of Geosciences, 2021)

FOXA2 inhibits doxorubicin-induced apoptosis via transcriptionally activating HBP rate-limiting enzyme GFPT1 in HCC cells - Huang Huang; Yuhan Wang; Tianmiao Huang; Lingyan Wang; Yangzhi Liu; Qiong Wu; Ang Yu; Meiyun Shi; Xiaoyu Wang; Wenli Li; Jianing Zhang; Yubo Liu (Journal of Physiology and Biochemistry, 2021)

Recent improvements to the physical model of the Bohai Sea, the Yellow Sea and the East China Sea Operational Oceanography Forecasting System - Ang Li; Xueming Zhu; Yunfei Zhang; Shihe Ren; Miaoyin Zhang; Ziqing Zu; Hui Wang (Acta Oceanologica Sinica, 2021)

Carbon limitation overrides acidification in mediating soil microbial activity to nitrogen enrichment in a temperate grassland - Qiushi Ning; Stephan Hättenschwiler; Xiaotao Lü; Paul Kardol; Yunhai Zhang; Cunzheng Wei; Chengyuan Xu; Jianhui Huang; Ang Li; Junjie Yang; Jing Wang; Yang Peng; et al. (Global Change Biology, 2021)
Higher ecosystem nitrogen (N) inputs resulting from human activities often suppress soil microbial biomass and respiration, thereby altering biogeochemical cycling. Soil acidification and carbon (C) limitation may drive these microbial responses, yet their relative importance remains elusive, which limits our understanding of the longer term effects of increasing N inputs. In a field experiment with continuous N addition at seven different rates from 0 to 50 g N m −2 year −1 over 6 years in a temperate grassland of Inner Mongolia, China, we examined the responses of soil microbial biomass and respiration to changes in soil acidity and C availability by adding lime and/or glucose to soil samples. Soil microbial biomass and respiration did only weakly respond to increasing soil pH, but increased strongly in response to higher C availability with increasing N addition rates. Soil net N immobilization increased in response to glucose addition, and soil microbial biomass increased at higher rates than microbial respiration along the gradient of previous N addition rates, both suggesting increasingly reinforced microbial C limitation with increasing N addition. Our results provide clear evidence for strong N‐induced microbial C limitation, but only little support for soil acidity effects within the initial pH range of 4.73–7.86 covered by our study. Field data support this conclusion by showing reduced plant C allocation belowground in response to N addition, resulting in soil microbial C starvation over the long term. In conclusion, soil microbial biomass and respiration under N addition were strongly dependent on C availability, most likely originating from plant belowground C inputs, and was much less affected by changes in soil pH. Our data help clarify a long‐standing debate about how increasing N input rates affect soil microbial biomass and respiration, and improve the mechanistic understanding of the linkages between ecosystem N enrichment and C cycling.

Developing the non‐dimensional framework for water distribution formulation to evaluate sprinkler irrigation* - Ang Li; Xinyuan Mu; Xia Zhao; Jiamin Xu; Majid Khayatnezhad; Reza Lalehzari (Irrigation and Drainage, 2021)
Improving the application efficiency and leaching of solutes from the root zone in a sprinkler irrigation system are directly related to the uniformity of water distribution at the field surface. The coefficient of uniformity and distribution uniformity are affected by changes in wind speed and its direction, sprinkler characteristics and variations in operating pressure. The objective of this paper is to present modified equations for evaluating pressurized irrigation systems based on non‐dimensional infiltrated depths. The equations were obtained by four data groups including the average of the measured infiltration depths in any quarter. Coefficient of uniformity (CU), distribution uniformity (DU), application efficiency ( E a ) and deep percolation (DP) were used as performance indicators to evaluate the sprinkler irrigation system. The suggested method was compared to the existing approach to assess the evaluation indicators. Three data sets of observed information for wheel‐move, permanent solid set and semi‐solid set irrigation systems were collected in Chaharmahal and Bakhtiari provinces to evaluate the proposed formulation. Furthermore, the relationships between CU and DU were analysed for three scenarios of infiltration depth. Results show that the application efficiency was 12% less than previous equations because of using four average values.

Influences of Loading Method and Notch Type on Rock Fracture Toughness Measurements: From the Perspectives of T-Stress and Fracture Process Zone - Mingdong Wei; Feng Dai; Yi Liu; Ang Li; Zelin Yan (Rock Mechanics and Rock Engineering, 2021)

Quantifying and Modeling of In Situ Stress Evolutions of Coal Reservoirs for Helium, Methane, Nitrogen and CO2 Depletions - Xiaowei Hou; Shimin Liu; Guofu Li; Yanming Zhu; Ang Liu (Rock Mechanics and Rock Engineering, 2021)

Phylogenomic Analyses of a Clade Within the Family Flavobacteriaceae Suggest Taxonomic Reassignments of Species of the Genera Algibacter, Hyunsoonleella, Jejuia, and Flavivirga, and the Proposal of Pseudalgibacter gen. nov. and Pseudalgibacter alginicilyticus comb. nov. - Miao Li; Ling-Zhi Hou; Xing-Hao Xu; Xiao-Xiao Wang; Ming-Can Zheng; Yan-Jiao Zhang; Ang Liu (Current Microbiology, 2021)

Experimental investigation of temperature distribution and spontaneous combustion tendency of coal gangue stockpiles in storage - Ang Li; Changkun Chen; Jie Chen; Peng Lei; Yulun Zhang (Environmental Science and Pollution Research, 2021)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

Numerical Analysis of the Water-blocking Performance of a Floor with a Composite Structure under Fluid–solid Coupling - Ang Li; Qian Mu; Li Ma; Chaoyang Liu; Shengquan Wang; Feng Wang; Lin Mou (Mine Water and the Environment, 2021)

Distribution, sources, and risk assessment of polycyclic aromatic hydrocarbons (PAHs) in surface sediments from Daya Bay, South China - Bin Han; Dongyang Cui; Ang Liu; Qian Li; Li Zheng (Environmental Science and Pollution Research, 2021)

Dynamics and multi‐annual fate of atmospherically deposited nitrogen in montane tropical forests - Ang Wang; Dexiang Chen; Oliver L. Phillips; Per Gundersen; Xulun Zhou; Geshere A. Gurmesa; Shanlong Li; Weixing Zhu; Erik A. Hobbie; Xueyan Wang; Yunting Fang (Global Change Biology, 2021)
The effects of nitrogen (N) deposition on forests largely depend on its fate after entering the ecosystem. While several studies have addressed the forest fate of N deposition using 15 N tracers, the long‐term fate and redistribution of deposited N in tropical forests remains unknown. Here, we applied 15 N tracers to examine the fates of deposited ammonium ( ) and nitrate ( ) separately over 3 years in a primary and a secondary tropical montane forest in southern China. Three months after 15 N tracer addition, over 60% of 15 N was retained in the forests studied. Total ecosystem retention did not change over the study period, but between 3 months and 3 years following deposition 15 N recovery in plants increased from 10% to 19% and 13% to 22% in the primary and secondary forests, respectively, while 15 N recovery in the organic soil declined from 16% to 2% and 9% to 2%. Mineral soil retained 50% and 35% of 15 N in the primary and secondary forests, with retention being stable over time. The total ecosystem retention of the two N forms did not differ significantly, but plants retained more than and the organic soil more than . Mineral soil did not differ in and retention. Compared to temperate forests, proportionally more 15 N was distributed to mineral soil and plants in these tropical forests. Overall, our results suggest that atmospherically deposited and is rapidly lost in the short term (months) but thereafter securely retained within the ecosystem, with retained N becoming redistributed to plants and mineral soil from the organic soil. This long‐term N retention may benefit tropical montane forest growth and enhance ecosystem carbon sequestration.

Frequency Characteristics of Acoustic Emissions Induced by Crack Propagation in Rock Tensile Fracture - Ruochen Jiang; Feng Dai; Yi Liu; Ang Li; Peng Feng (Rock Mechanics and Rock Engineering, 2021)

Dynamic evaluation and spatiotemporal evolution of China’s industrial water use efficiency considering undesirable output - Changfeng Shi; Xinyun Zeng; Qianwen Yu; Junyuan Shen; Ang Li (Environmental Science and Pollution Research, 2021)

TRIC-A regulates intracellular Ca2+ homeostasis in cardiomyocytes - Xinyu Zhou; Ang Li; Pei-hui Lin; Jingsong Zhou; Jianjie Ma (Pflügers Archiv - European Journal of Physiology, 2021)
Trimeric intracellular cation (TRIC) channels have been identified as monovalent cation channels that are located in the ER/SR membrane. Two isoforms discovered in mammals are TRIC-A (TMEM38a) and TRIC-B (TMEM38b). TRIC-B ubiquitously expresses in all tissues, and TRIC-B −/− mice is lethal at the neonatal stage. TRIC-A mainly expresses in excitable cells. TRIC-A −/− mice survive normally but show abnormal SR Ca 2+ handling in both skeletal and cardiac muscle cells. Importantly, TRIC-A mutations have been identified in human patients with stress-induced arrhythmia. In the past decade, important discoveries have been made to understand the structure and function of TRIC channels, especially its role in regulating intracellular Ca 2+ homeostasis. In this review article, we focus on the potential roles of TRIC-A in regulating cardiac function, particularly its effects on intracellular Ca 2+ signaling of cardiomyocytes and discuss the current knowledge gaps.

Antimonate removal by diatomite modified with Fe-Mn oxides: application and mechanism study - Qiu-Yi Dong; Yu-Chun Fang; Bin Tan; Aura Ontiveros-Valencia; Ang Li; He-Ping Zhao (Environmental Science and Pollution Research, 2021)

Reclassification of Algibacter wandonensis as a Later Heterotypic Synonym of Algibacter lectus Based on Whole-Genome Sequence Analysis - Ang Liu; Hui Wang; Yuan-Yuan Yang; Qing-Jie Xue; Xiu-Zhen Li (Current Microbiology, 2021)

Dynamic Compression–Shear Response and Failure Criterion of Rocks with Hydrostatic Confining Pressure: An Experimental Investigation - Hongbo Du; Feng Dai; Mingdong Wei; Ang Li; Zelin Yan (Rock Mechanics and Rock Engineering, 2021)

Antifungal Effects of Fusion Puroindoline B on the Surface and Intracellular Environment of Aspergillus flavus - Ping-Ping Tian; Yang-Yong Lv; Ang Lv; Wen-Jing Yuan; Shuai-Bing Zhang; Na Li; Yuan-Sen Hu (Probiotics and Antimicrobial Proteins, 2021)

Construction of high-density genetic maps defined sex determination region of the Y chromosome in spinach - Li’ang Yu; Xiaokai Ma; Ban Deng; Jingjing Yue; Ray Ming (Molecular Genetics and Genomics, 2021)

Mechanical and Failure Characteristics of Rock-coal-rock Combined Body under Different Strain Rates: A Numerical Study from Micro Perspective - Shu-ning Dong; Ang Li; Ya-dong Ji; Yu-xuan Yang; Qian Mu (Geotechnical and Geological Engineering, 2021)

Pregabalin-associated stuttering and frequent blepharospasm: case report and review. - Lingzhi Ge; Ang Li; Ni Wang; Ping Li; Hongyan Xin; Wenfei Li (DARU Journal of Pharmaceutical Sciences, 2020)
Herpes zoster is an acute, painful, herpes skin disease caused by varicella-zoster virus, which may cause viral meningitis. Pregabalin has been shown to be efficacious in the treatment of pain in patients with herpes zoster. However, it has the side effects of neurotoxicity. We describe a 68-year-old female patient with herpes zoster, and she was treated with pregabalin. The patient presented with stuttering and frequent blepharospasm after 3 days of pregabalin treatment. Pregabalin was discontinued, the symptoms of stuttering and frequent blepharospasm completely resolved without any special treatment after one week. In this case, the etiology of stuttering and frequent blepharospasm may be related to pregabalin. Clinicians should be alert to the rare symptoms associated with the use of pregabalin.

Deinococcus detaillensis sp. nov., isolated from humus soil in Antarctica - Kun Zhang; Jing Zhu; Shuai Li; Manik Prabhu Narsing Rao; Ning-Mei Li; Ang-Yang Guo; Zhao Jiang; Qi-Yong Tang; Yi Wan; Zhi-Dong Zhang; Wen-Jun Li (Archives of Microbiology, 2020)

Numerical Simulation of a Polar Ship Moving in Level Ice Based on a One-Way Coupling Method - Bao-Yu Ni; Zi-Wang Chen; Kai Zhong; Xin-Ang Li; Yan-Zhuo Xue (Journal of Marine Science and Engineering, 2020)
In most previous ice–ship interaction studies involving fluid effects, ice was taken as unbreakable. Building breakable level ice on water domain is still a big challenge in numerical simulation. This paper overcomes this difficulty and presents a numerical modeling of a ship moving in level ice on the water by using a one-way CFD-DEM (computational fluid dynamics-discrete element method) coupling method. The detailed numerical processes and techniques are introduced. The ice crack propagation process including radial and circular cracks have been observed. Numerical results are compared with previous experimental data and good agreement has been achieved. The results show that water resistance is an order of magnitude smaller than ice resistance during the ice-breaking process. Ice resistance shows strong oscillation along with ice failure process, which are affected by ship speed and ice thickness significantly.

OP16 induces deadly autophagy and apoptosis of cells by inhibiting Akt in esophageal squamous cell carcinoma - Guiqin Hou; Ang Jia; Li Yang; Yu Zhao; Yi Hu; Wuduo Zhao; Wen Zhao; Hong-Min Liu; Zhaoming Lu (Molecular and Cellular Biochemistry, 2020)

Vascular KATP channels protect from cardiac dysfunction and preserve cardiac metabolism during endotoxemia - Qadeer Aziz; Jianmin Chen; Amie J Moyes; Yiwen Li; Naomi A Anderson; Richard Ang; Dunja Aksentijevic; Sonia Sebastian; Adrian J Hobbs; Christoph Thiemermann; Andrew Tinker (Journal of Molecular Medicine, 2020)
K ATP channels in the vasculature composed of Kir6.1 regulate vascular tone and may contribute to the pathogenesis of endotoxemia. We used mice with cell-specific deletion of Kir6.1 in smooth muscle (smKO) and endothelium (eKO) to investigate this question. We found that smKO mice had a significant survival disadvantage compared with their littermate controls when treated with a sub-lethal dose of lipopolysaccharide (LPS). All cohorts of mice became hypotensive following bacterial LPS administration; however, mean arterial pressure in WT mice recovered to normal levels, whereas smKO struggled to overcome LPS-induced hypotension. In vivo and ex vivo investigations revealed pronounced cardiac dysfunction in LPS-treated smKO, but not in eKO mice. Similar results were observed in a cecal slurry injection model. Metabolomic profiling of hearts revealed significantly reduced levels of metabolites involved in redox/energetics, TCA cycle, lipid/fatty acid and amino acid metabolism. Vascular smooth muscle-localised K ATP channels have a critical role in the response to systemic infection by normalising cardiac function and haemodynamics through metabolic homeostasis. Key messages • Mice lacking vascular K ATP channels are more susceptible to death from infection. • Absence of smooth muscle K ATP channels depresses cardiac function during infection. • Cardiac dysfunction is accompanied by profound changes in cellular metabolites. • Findings from this study suggest a protective role for vascular K ATP channels in response to systemic infection.

Effect of Bedding Angle and Mineral Composition on Mechanical Properties and Fracture Behavior of Phyllite Under Unloading Confining Pressures - Xiaolong Guo; Zhongsheng Tan; Xiao Wang; Ang Li; Zhongjun Ma; Yongsheng Wu (Geotechnical and Geological Engineering, 2020)

Quantitative reconstruction of Holocene millennial-scale precipitation in the Asian monsoon margin of northwest China, revealed by phytolith assemblages from calcareous root tubes in the Tengger Desert - Youhong Gao; Zhuolun Li; Ruixia Zhu; Nai’ang Wang (Climate Dynamics, 2020)

Spatial Accessibility to Shopping Malls in Nanjing, China: Comparative Analysis with Multiple Transportation Modes - Ang Li; Jie Chen; Tianlu Qian; Wenhan Zhang; Jiechen Wang (Chinese Geographical Science, 2020)

Data Analysis and Key Parameters of Typical Water Hazard Control Engineering in Coal Mines of China - Lin Mou; Shuning Dong; Wanfang Zhou; Wei Wang; Ang Li; Zhiyuan Shi (Mine Water and the Environment, 2020)

Effects of osmotic stress on the expression profiling of aquaporin genes in the roughskin sculpin (Trachidermus fasciatus) - Qian Ma; Xinfu Liu; Ang Li; Shufang Liu; Zhimeng Zhuang (Acta Oceanologica Sinica, 2020)

Colletotrichum fructicola STE50 is required for vegetative growth, asexual reproduction, appressorium formation, pathogenicity and the response to external stress - Yan-ying Chen; Jun-ang Liu; Shi-qiang Jiang; He Li; Guo-ying Zhou (Journal of Plant Pathology, 2020)

Litorilituus lipolyticus sp. nov., isolated from intertidal sand of the Yellow Sea in China, and emended description of Colwellia asteriadis - Ang Liu; Yan-Jiao Zhang; Qing-Jie Xue; Hui Wang; Yuan-Yuan Yang; Feng Du; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2020)

IGS real-time service for global ionospheric total electron content modeling - Zishen Li; Ningbo Wang; Manuel Hernández-Pajares; Yunbin Yuan; Andrzej Krankowski; Ang Liu; Jiuping Zha; Alberto García-Rigo; David Roma-Dollase; Heng Yang; Denis Laurichesse; Alexis Blot (Journal of Geodesy, 2020)

Effects of osmotic stress on Na+/K+-ATPase, caspase 3/7 activity, and the expression profiling of sirt1, hsf1, and hsp70 in the roughskin sculpin (Trachidermus fasciatus) - Qian Ma; JieHua Kuang; Xinfu Liu; Ang Li; Wenrong Feng; Zhimeng Zhuang (Fish Physiology and Biochemistry, 2020)

Enhanced adsorption performance and regeneration of magnetic Fe3O4 nanoparticles assisted extracellular polymeric substances in sulfonamide-contaminated water - Shanshan Pi; Ang Li; Di Cui; Zhou Su; Lu Zhou; Fang Ma (Environmental Science and Pollution Research, 2020)

Identification of the magnesium transport (MGT) family in Poncirus trifoliata and functional characterization of PtrMGT5 in magnesium deficiency stress - Xiao Liu; Ling-Xia Guo; Li-Juan Luo; Yong-Zhong Liu; Shu-Ang Peng (Plant Molecular Biology, 2019)

The mediated role of complement C3 in PM2.5 exposure and type 2 diabetes mellitus: an elderly panel study in Beijing, China - Yuanren Tong; Lu Pei; Kai Luo; Meiduo Zhao; Jing Xu; Ang Li; Runkui Li; Mingan Yang; Qun Xu (Environmental Science and Pollution Research, 2019)

Flavivirga rizhaonensis sp. nov., a marine bacterium isolated from intertidal sand - Ang Liu; Hong-Mei Liu; Feng Du; Shuang Wang; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Qing-Jie Xue; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2019)

Preparation of Deoxycholate-Modified Docetaxel-Cimetidine Complex Chitosan Nanoparticles to Improve Oral Bioavailability - Yingxin Xu; Tianxu Fang; Yifan Yang; Li’ang Sun; Qi Shen (AAPS PharmSciTech, 2019)

Analysis of a Complex Flexural Toppling Failure of Large Underground Caverns in Layered Rock Masses - Ang Li; Feng Dai; Nuwen Xu; Gongkai Gu; Zhonghua Hu (Rock Mechanics and Rock Engineering, 2019)

Regional ionospheric TEC modeling based on a two-layer spherical harmonic approximation for real-time single-frequency PPP - Zishen Li; Ningbo Wang; Liang Wang; Ang Liu; Hong Yuan; Kefei Zhang (Journal of Geodesy, 2019)

Proteomics analysis of Schwann cell-derived exosomes: a novel therapeutic strategy for central nervous system injury - Zhijian Wei; Baoyou Fan; Han Ding; Yang Liu; Haoshuai Tang; Dayu Pan; Jiaxiao Shi; Pengyuan Zheng; Hongyu Shi; Heng Wu; Ang Li; Shiqing Feng (Molecular and Cellular Biochemistry, 2019)

Strain identification and metabolites isolation of Aspergillus capensis CanS-34A from Brassica napus - Jing Qin; Ang Lyu; Qing-hua Zhang; Long Yang; Jing Zhang; Ming-de Wu; Guo-qing Li (Molecular Biology Reports, 2019)

Treatment of Periodontal Bone Defects with Stem Cells from Inflammatory Dental Pulp Tissues in Miniature Swine - Ye Li; Xi Nan; Tian-Yu Zhong; Tong Li; Ang Li (Tissue Engineering and Regenerative Medicine, 2019)

Spatial variation in the effects of air pollution on cardiovascular mortality in Beijing, China - Wenjing Li; Lu Pei; Ang Li; Kai Luo; Yang Cao; Runkui Li; Qun Xu (Environmental Science and Pollution Research, 2019)

Disruption of bone morphogenetic protein type IA receptor in osteoblasts impairs bone quality and bone strength in mice - Quanwei Bao; Ang Li; Sixu Chen; Jianquan Feng; Huayu Liu; Hao Qin; Junfeng Li; Daocheng Liu; Yue Shen; Zhaowen Zong (Cell and Tissue Research, 2018)

Differential responses of canopy nutrients to experimental drought along a natural aridity gradient - Wentao Luo; Xiaoan Zuo; Wang Ma; Chong Xu; Ang Li; Qiang Yu; Alan K. Knapp; Roberto Tognetti; Feike A. Dijkstra; Mai‐He Li; Guodong Han; Zhengwen Wang; et al. (Ecology, 2018)
The allocation and stoichiometry of plant nutrients in leaves reflect fundamental ecosystem processes, biotic interactions, and environmental drivers such as water availability. Climate change will lead to increases in drought severity and frequency, but how canopy nutrients will respond to drought, and how these responses may vary with community composition along aridity gradients is poorly understood. We experimentally addressed this issue by reducing precipitation amounts by 66% during two consecutive growing seasons at three sites located along a natural aridity gradient. This allowed us to assess drought effects on canopy nitrogen (N) and phosphorus (P) concentrations in arid and semiarid grasslands of northern China. Along the aridity gradient, canopy nutrient concentrations were positively related to aridity, with this pattern was driven primarily by species turnover (i.e., an increase in the relative biomass of N‐ and P‐rich species with increasing aridity). In contrast, drought imposed experimentally increased N but decreased P concentrations in plant canopies. These changes were driven by the combined effects of species turnover and intraspecific variation in leaf nutrient concentrations. In addition, the sensitivity of canopy N and P concentrations to drought varied across the three sites. Canopy nutrient concentrations were less affected by drought at drier than wetter sites, because of the opposing effects of species turnover and intraspecific variation, as well as greater drought tolerance for nutrient‐rich species. These contrasting effects of long‐term aridity vs. short‐term drought on canopy nutrient concentrations, as well as differing sensitivities among sites in the same grassland biome, highlight the challenge of predicting ecosystem responses to future climate change.

Influence of heterogeneity on mechanical and acoustic emission behaviours of stratified rock specimens - Ang Li; Guo-jian Shao; Jing-bo Su; Yang Sun; Tian-tang Yu; Hou-gai Shi (European Journal of Environmental and Civil Engineering, 2018)

Statistical landslide susceptibility assessment in a dynamic environment: A case study for Lanzhou City, Gansu Province, NW China - Jewgenij Torizin; Li-chao Wang; Michael Fuchs; Bin Tong; Dirk Balzer; Li-qin Wan; Dirk Kuhn; Ang Li; Liang Chen (Journal of Mountain Science, 2018)

Nitrogen removal performance and microbial community of an enhanced multistage A/O biofilm reactor treating low-strength domestic wastewater - Han Chen; Ang Li; Qiao Wang; Di Cui; Chongwei Cui; Fang Ma (Biodegradation, 2018)

Long-term study on seasonal changes in floristic composition and structure of marine macroalgal communities along the coast of Northern Taiwan, southern East China Sea - Showe-Mei Lin; Li-Chun Tseng; Put O. Ang; John Bolton; Li-Chia Liu (Marine Biology, 2018)

Degradation reaction of Diazo reactive black 5 dye with copper (II) sulfate catalyst in thermolysis treatment - Yen-Yie Lau; Yee-Shian Wong; Tze-Zhang Ang; Soon-An Ong; Nabilah Aminah Lutpi; Li-Ngee Ho (Environmental Science and Pollution Research, 2018)

Erratum to: Forskolin Induces Hyperphosphorylation of Tau Accompanied by Cell Cycle Reactivation in Primary Hippocampal Neurons - Hai-Hong Wang; Yan Li; Ang Li; Fang Yan; Zhen-Lin Li; Zhong-Ying Liu; Lei Zhang; Jian Zhang; Wei-Ren Dong; Lin Zhang (Molecular Neurobiology, 2018)

Forskolin Induces Hyperphosphorylation of Tau Accompanied by Cell Cycle Reactivation in Primary Hippocampal Neurons - Hai-Hong Wang; Yan Li; Ang Li; Fang Yan; Zhen-Lin Li; Zhong-Ying Liu; Lei Zhang; Jian Zhang; Wei-Ren Dong; Lin Zhang (Molecular Neurobiology, 2018)

Preparation, Gel Electrophoresis Analysis, and Nutritional Evaluation of a Functional Krill Protein Concentrate with Low Fluoride Level from Antarctic krill ( Euphausia superba ) - Li’ang Yin; Xiaoming Jiang; Yan Fan; Jingfeng Wang; Changhu Xue; Yong Xue (Journal of Aquatic Food Product Technology, 2017)

Physiological and transcriptional analysis reveals pathways involved in iron deficiency chlorosis in fragrant citrus - Long-Fei Jin; Yong-Zhong Liu; Wei Du; Li-Na Fu; Syed Bilal Hussain; Shu-Ang Peng (Tree Genetics & Genomes, 2017)

Long-term variation in the salinity of the Southern Yellow Sea Cold Water Mass, 1976–2006 - Ang Li; Fei Yu; Guangcheng Si; Chuanjie Wei (Journal of Oceanography, 2017)

Nitrogen removal and microbial community shift in an aerobic denitrification reactor bioaugmented with a Pseudomonas strain for coal-based ethylene glycol industry wastewater treatment - Cong Du; Chong-Wei Cui; Shan Qiu; Sheng-Nan Shi; Ang Li; Fang Ma (Environmental Science and Pollution Research, 2017)

Analyzing the flavor compounds in Chinese traditional fermented shrimp pastes by HS-SPME-GC/MS and electronic nose - Yan Fan; Li’ang Yin; Yong Xue; Zhaojie Li; Hu Hou; Changhu Xue (Journal of Ocean University of China, 2017)

Role of the Helix in Talin F3 Domain (F3 Helix) in Talin-Mediated Integrin Activation - Ang Li; Qiang Guo; Ailin Wei; Yaliang Zhou; Weiming Hu (Cell Biochemistry and Biophysics, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Adsorption behavior of tetracycline by extracellular polymeric substrates extracted from Klebsiella sp. J1 - Ang Li; Shanshan Pi; Wei Wei; Ting Chen; Jixian Yang; Fang Ma (Environmental Science and Pollution Research, 2016)

Transgenerational Inheritance of Paternal Neurobehavioral Phenotypes: Stress, Addiction, Ageing and Metabolism - Ti-Fei Yuan; Ang Li; Xin Sun; Huan Ouyang; Carlos Campos; Nuno B. F. Rocha; Oscar Arias-Carrión; Sergio Machado; Gonglin Hou; Kwok Fai So (Molecular Neurobiology, 2016)

Prescreening, identification and harvesting of microalgae with antibacterial activity - Ang Li; Ling Zhang; Zhen-yu Zhao; Sha-sha Ma; Meng Wang; Ping-huai Liu (Biologia, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Transcriptome Sequencing of the Sweet Potato Progenitor (Ipomoea Trifida (H.B.K.) G. Don.) and Discovery of Drought Tolerance Genes - Qinghe Cao; Ang Li; Jinyang Chen; Yu Sun; Jun Tang; An Zhang; Zhilin Zhou; Donglan Zhao; Daifu Ma; Shan Gao (Tropical Plant Biology, 2016)

Effects of Land Use Change on Phosphorus Levels in Surface Waters—a Case Study of a Watershed Strongly Influenced by Agriculture - Bin Zhou; Yaping Xu; Rolf D. Vogt; Xueqiang Lu; Xuemei Li; Xiaowen Deng; Ang Yue; Liang Zhu (Water, Air, & Soil Pollution, 2016)

Boron deficiency affects root vessel anatomy and mineral nutrient allocation of Poncirus trifoliata (L.) Raf. - Li Mei; Qiaohong Li; Huan Wang; Ou Sheng; Shu-ang Peng (Acta Physiologiae Plantarum, 2016)

Early–middle Holocene hydroclimate changes in the Asian monsoon margin of northwest China inferred from Huahai terminal lake records - Zhuolun Li; Nai’ang Wang; Hongyi Cheng; Yu Li (Journal of Paleolimnology, 2016)

Analysis of the sucrose synthase gene family in tobacco: structure, phylogeny, and expression patterns - Zhong Wang; Pan Wei; Mingzhu Wu; Yalong Xu; Feng Li; Zhaopeng Luo; Jianfeng Zhang; Ang Chen; Xiaodong Xie; Peijian Cao; Fucheng Lin; Jun Yang (Planta, 2015)

Association Between a Variant in ADAMTS5 and the Susceptibility to Hepatocellular Carcinoma in a Chinese Han Population - Chongyi Li; Yanli Xiong; Zhaoyang Zhong; Shiheng Zhang; Yu Peng; Lin’ang Wang; Nan Dai; Mengxia Li; Tao Ren; Lixia Gan; Dong Wang (Cell Biochemistry and Biophysics, 2015)

Transcript and metabolite alterations increase ganoderic acid content in Ganoderma lucidum using acetic acid as an inducer - Ang Ren; Xiong-Biao Li; Zhi-Gang Miao; Liang Shi; Ai-Liang Jaing; Ming-Wen Zhao (Biotechnology Letters, 2014)

Identification of fucans from four species of sea cucumber by high temperature 1H NMR - Nian Wu; Shiguo Chen; Xingqian Ye; Guoyun Li; Li’ang Yin; Changhu Xue (Journal of Ocean University of China, 2014)

The role of activated adenosine receptors in degranulation of human LAD2 mast cells - Chi Ting Leung; Ang Li; Juni Banerjee; Zhan-Guo Gao; Taku Kambayashi; Kenneth A. Jacobson; Mortimer M. Civan (Purinergic Signalling, 2014)

Functions of the nicotinamide adenine dinucleotide phosphate oxidase family in G anoderma lucidum : an essential role in ganoderic acid biosynthesis regulation, hyphal branching, fruiting body development, and oxidative‐stress resistance - Dashuai Mu; Chenyang Li; Xuchen Zhang; Xiongbiao Li; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2014)
Summary G anoderma lucidum has drawn worldwide interest with regard to its secondary metabolism and pharmaceutical activity. However, the development of such research has been limited because of a lack of basic biological knowledge. Nicotinamide adenine dinucleotide phosphate oxidases (Nox) have recently been highlighted because of the many important biological roles in plants and animals; however, the exact functions of Nox are still not fully understood in fungi. In this study, we identified two N ox isoforms ( NoxA and NoxB ) and a regulator, NoxR . RNA interference was used, and silencing of the Nox isoforms and NoxR expression indicated a central role for these genes in hyphal branching, fruiting body development, reactive oxygen species ( ROS ) generation, ROS resistance and ganoderic acid biosynthesis regulation. Further mechanistic investigation revealed that N ox‐generated ROS elevated cytosolic Ca 2+ levels by activating a plasma membrane Ca 2+ influx pathway, thereby inducing the Ca 2+ signal pathway to regulate ganoderic acid biosynthesis and hyphal branching. Importantly, our results highlight the N ox functions in signal crosstalk between ROS and Ca 2+ , and these findings provide an excellent opportunity to identify the potential pathway linking ROS networks to calcium signalling in fungi and suggest that plants, animals and fungi share a conserved signal‐crosstalk mechanism.

Variations in nitrogen-15 natural abundance of plant and soil systems in four remote tropical rainforests, southern China - Ang Wang; Yun-Ting Fang; De-Xiang Chen; Keisuke Koba; Akiko Makabe; Yi-De Li; Tu-Shou Luo; Muneoki Yoh (Oecologia, 2014)

Overexpression of CsCLCc, a Chloride Channel Gene from Poncirus trifoliata, Enhances Salt Tolerance in Arabidopsis - Qingjiang Wei; Yongzhong Liu; Gaofeng Zhou; Qiaohong Li; Chengquan Yang; Shu-ang Peng (Plant Molecular Biology Reporter, 2013)

Changes in soil organic carbon and total nitrogen stocks after conversion of meadow to cropland in Northeast China - Fan Ding; Ya-Lin Hu; Lu-Jun Li; Ang Li; Shengwei Shi; Pei-Yong Lian; De-Hui Zeng (Plant and Soil, 2013)

Carbonate formation and water level changes in a paleo-lake and its implication for carbon cycle and climate change, arid China - Yu Li; Nai’ang Wang; Zhuolun Li; Xuehua Zhou; Chengqi Zhang; Yue Wang (Frontiers of Earth Science, 2013)

Purification, molecular cloning, and antimicrobial activity of peptides from the skin secretion of the black-spotted frog, Rana nigromaculata - Ang Li; Yong Zhang; Che Wang; Geng Wu; Zhenchun Wang (World Journal of Microbiology and Biotechnology, 2013)

Climatic and environmental change in Yanchi Lake, Northwest China since the Late Glacial: A comprehensive analysis of lake sediments - Yu Li; Nai’ang Wang; Zhuolun Li; Xuehua Zhou; Chengqi Zhang (Journal of Geographical Sciences, 2013)

Dynamic mobilization of PGC-1α mediates mitochondrial biogenesis for the protection of RGC-5 cells by resveratrol during serum deprivation - Shida Chen; Qian Fan; Ang Li; Dongjiang Liao; Jian Ge; Alan M. Laties; Xiulan Zhang (Apoptosis, 2013)

Polymorphism of TaSAP1-A1 and its association with agronomic traits in wheat - Jianzhong Chang; Jianan Zhang; Xinguo Mao; Ang Li; Jizeng Jia; Ruilian Jing (Planta, 2013)

Nitrogen Translocation to Fresh Litter in Northern Hardwood Forest - Ang Li; Timothy J. Fahey (Ecosystems, 2013)

Molecular characterization and expression analysis of GlHMGS, a gene encoding hydroxymethylglutaryl-CoA synthase from Ganoderma lucidum (Ling-zhi) in ganoderic acid biosynthesis pathway - Ang Ren; Xiang Ouyang; Liang Shi; Ai-Liang Jiang; Da-Shuai Mu; Meng-Jiao Li; Qin Han; Ming-Wen Zhao (World Journal of Microbiology and Biotechnology, 2013)

Isolation and characterization of polymorphic microsatellite markers in the fish Garra orientalis (oriental sucking barb) - Li-Wei Su; Zhi-Zhi Liu; Cong-Tao Wang; Zhen Zeng; Ang-Yu Liu; Wen-Qiao Tang; Jin-Quan Yang (Conservation Genetics Resources, 2013)

Lake evaporation: A possible factor affecting lake level changes tested by modern observational data in arid and semi-arid China - Yu Li; Nai’ang Wang; Zhuolun Li; Ning Ma; Xuehua Zhou; Chengqi Zhang (Journal of Geographical Sciences, 2013)

Tree‐ring‐based temperature reconstruction for the northern Greater Higgnan Mountains, China, since A.D. 1717 - Tongwen Zhang; Yujiang Yuan; Wenshou Wei; Shulong Yu; Ruibo Zhang; Huaming Shang; Feng Chen; Zi'ang Fan; Li Qin (International Journal of Climatology, 2013)
In this paper, ring‐width chronologies of pine trees ( Pinus sylvestris var. mongolica ) from one sampling site in the northern Greater Higgnan Mountains, China, were constructed. The results of growth‐climate responses show that mean temperature is the limiting factor affecting radial growth of pine trees in the study area. Consequently, mean temperature from May to October from 1717 to 2008 has been reconstructed using the standard chronology. For the calibrated period (1957‐2008), the explained variance of the reconstruction is 57%. The characteristics of the reconstruction expose that mean temperature has increased since the 1970s, and the decade 2000s and 1990s are also ranked as the warm decades on record. However, this period from 1970s to now is not exceptional within the past 300 years. By applying an 11‐year moving average to the reconstruction, three warm periods and three cold periods are evident. The warm and cold periods of the reconstructed mean temperature correspond well with other reconstructions. Power spectral and wavelet analysis demonstrated the existence of significant ∼70‐ and ∼100‐year cycles of variability. Furthermore, the reconstruction and North Atlantic Oscillation Index showed a significant positive correlation ( r = 0.34, n = 136, p

Effects of Selenium Source and Level on Growth Performance, Tissue Selenium Concentrations, Antioxidation, and Immune Functions of Heat-Stressed Broilers - Xiudong Liao; Lin Lu; Sufen Li; Songbai Liu; Liyang Zhang; Guangying Wang; Ang Li; Xugang Luo (Biological Trace Element Research, 2012)

Reservoir information extraction using a fractional fourier transform and a smooth pseudo Wigner-Ville distribution - Zhu-Wen Wang; Xiao-Li Wang; Min Xiang; Jing-Hua Liu; Xue-Ang Zhang; Chuang Yang (Applied Geophysics, 2012)

Boron distribution and mobility in navel orange grafted on citrange and trifoliate orange - Gui-Dong Liu; Rui-Dong Wang; Li-Shu Wu; Shu-Ang Peng; Yun-Hua Wang; Cun-Cang Jiang (Plant and Soil, 2012)

Holocene climate cycles in northwest margin of Asian monsoon - Yu Li; Nai’ang Wang; Zhuolun Li; Xuehua Zhou; Chengqi Zhang (Chinese Geographical Science, 2012)

Microbial community analysis of three municipal wastewater treatment plants in winter and spring using culture-dependent and culture-independent methods - Di Cui; Ang Li; Si Zhang; Changlong Pang; Jixian Yang; Jingbo Guo; Fang Ma; Jihua Wang; Nanqi Ren (World Journal of Microbiology and Biotechnology, 2012)

Diversity‐dependent stability under mowing and nutrient addition: evidence from a 7‐year grassland experiment - Haijun Yang; Lin Jiang; Linghao Li; Ang Li; Mingyu Wu; Shiqiang Wan (Ecology Letters, 2012)
Ecology Letters (2012) Abstract Anthropogenic perturbations may affect biodiversity and ecological stability as well as their relationships. However, diversity–stability patterns and associated mechanisms under human disturbances have rarely been explored. We conducted a 7‐year field experiment examining the effects of mowing and nutrient addition on the diversity and temporal stability of herbaceous plant communities in a temperate steppe in northern China. Mowing increased population and community stability, whereas nutrient addition had the opposite effects. Stability exhibited positive relationships with species richness at population, functional group and community levels. Treatments did not alter these positive diversity–stability relationships, which were associated with the stabilising effect of species richness on component populations, species asynchrony and portfolio effects. Despite the difficulty of pinpointing causal mechanisms of diversity–stability patterns observed in nature, our results suggest that diversity may still be a useful predictor of the stability of ecosystems confronted with anthropogenic disturbances.

Relationship between triphasic mechanical properties of articular cartilage and osteoarthritic grade - HaiJun Niu; ChengRui Liu; Ang Li; Qing Wang; YueXiang Wang; DeYu Li; YuBo Fan (Science China Life Sciences, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Development of a simple and efficient transformation system for the basidiomycetous medicinal fungus Ganoderma lucidum - Liang Shi; Xing Fang; Mengjiao Li; Dashuai Mu; Ang Ren; Qi Tan; Mingwen Zhao (World Journal of Microbiology and Biotechnology, 2012)

Characterization of a compound bioflocculant produced by mixed culture of Rhizobium radiobacter F2 and Bacillus sphaeicus F6 - Lili Wang; Fang Ma; Yuanyuan Qu; Dezhi Sun; Ang Li; Jingbo Guo; Bing Yu (World Journal of Microbiology and Biotechnology, 2011)

Transgenic expression of TaMYB2A confers enhanced tolerance to multiple abiotic stresses in Arabidopsis - Xinguo Mao; Dongsheng Jia; Ang Li; Hongying Zhang; Shanjun Tian; Xiaoke Zhang; Jizeng Jia; Ruilian Jing (Functional & Integrative Genomics, 2011)

Study on algorithms of low SNR inversion of T 2 spectrum in NMR - Feng Lin; Zhu-Wen Wang; Jing-Ye Li; Xue-Ang Zhang; Yu-Long Jiang (Applied Geophysics, 2011)

TM4SF1: a tetraspanin-like protein necessary for nanopodia formation and endothelial cell migration - Andrew Zukauskas; Anne Merley; Dan Li; Lay-Hong Ang; Tracey E. Sciuto; Samantha Salman; Ann M. Dvorak; Harold F. Dvorak; Shou-Ching Shih Jaminet (Angiogenesis, 2011)

Maximum Grade Approach to Surplus Floodwater of Hyperconcentration Rivers in Flood Season and its Application - Xun-Gui Li; Xia Wei; Nai-Ang Wang; Hong-Yi Cheng (Water Resources Management, 2011)

Resource availability, species composition and sown density effects on productivity of experimental plant communities - Ang Li; Kechang Niu; Guozhen Du (Plant and Soil, 2011)

Estimates of individuals exposed to human metapneumovirus in a community-based Taiwanese population in 1999 - Chung-Guei Huang; Kuo-Chien Tsao; Tzou-Yien Lin; Yhu-Chering Huang; Li-Ang Lee; Tzu-Hou Chen; Ya-Ling Huang; Shin-Ru Shih (Archives of Virology, 2010)

Brain serotonin transporter in human methamphetamine users - Stephen J. Kish; Paul S. Fitzmaurice; Isabelle Boileau; Gregory A. Schmunk; Lee-Cyn Ang; Yoshiaki Furukawa; Li-Jan Chang; Dennis J. Wickham; Allan Sherwin; Junchao Tong (Psychopharmacology, 2009)

Measurements of nighttime nitrate radical concentrations in the atmosphere by long-path differential optical absorption spectroscopy - Suwen Li; Wenqing Liu; Pinhua Xie; Ang Li; Min Qin; Ke Dou (Advances in Atmospheric Sciences, 2007)

Genetic Variation in Hippophae rhamnoides ssp. sinensis (Elaeagnaceae) Revealed by RAPD Markers - Kun Sun; Wen Chen; Ruijun Ma; Xuelin Chen; Ang Li; Song Ge (Biochemical Genetics, 2006)

Historical desertification process in Hexi Corridor, China - Nai-ang Wang; Chun-hui Zhang; Gang Li; Hong-yi Cheng (Chinese Geographical Science, 2005)

Note: A Preliminary Study on Conservation Genetics of an Endangered Orchid (Paphiopedilum micranthum) from Southwestern China - Ang Li; Yi-bo Luo; Song Ge (Biochemical Genetics, 2002)